Catalytic aquathermolysis upgrading of heavy oil with MoS2 oil-in-dispersion emulsion - Yuchen Zhong; Jinghuan Liu; Jun Nan; Hongzuo Zhao; Xinfeng Ju; Xiongfei Li; Dong Wang; Binfei Li; Yongming Chai; Xufeng Lin; Jiqian Wang (Fuel, 2027)

Non-contact monitoring of grouper fry weaning in recirculating aquaculture systems: Efficacy of an automated stereo vision system - Cheng-Yuan Kuo; Rung-Chi Lin; Tzong-Yueh Chen; Pei-Ju Chiang (Aquacultural Engineering, 2027)

A novel approach for assessing the genuine thermal efficiency of high-pressure grinding roller (HPGR) crusher based on exergy analysis - Zhengyu Liu; Zhihao Liu; Xiaoming Liu; Bin Yang; Wei Liu; Jiawei Lin; Siqi Zhang; Wenjie Zou; Jun Zhang; Jinrong Ju; Jue Kou; Chunbao Sun; et al. (Minerals Engineering, 2026)

TGF-β-induced autophagy in pulmonary artery endothelial cells associated with chronic thromboembolic pulmonary hypertension - Ying-Ju Lai; Yen-Lin Huang; Ching-Yen Tsai; Po-Ru Chen; Chi-Jen Chang; Yung-Hsin Yeh; Celina De Almeida; Hsao-Hsun Hsu (Journal of Molecular Medicine, 2026)

Combined targeting poly (ADP-ribose) polymerase and receptor tyrosine kinase inhibits ovarian clear cell carcinoma progression through disrupted ribosome biogenesis - Chiao-Yun Lin; An-Shine Chao; Angel Chao; Ren-Chin Wu; Alice L. Yu; Chiung-Hui Fu; Yu-Chuan Teng; Ruby Yun-Ju Huang; Chyong-Huey Lai (Journal of Molecular Medicine, 2026)

Decadal stability and forensic reliability of petroleum biomarkers in tropical coastal environments: Validating laboratory kinetics against 10-year field residues - Ying-Ju Chang; Cheng-Ting Lin (Marine Pollution Bulletin, 2026)

Development of an isoform-discriminating RT-qPCR assay for transcript-level profiling of human ASAH2 in colorectal cancer cell models - You Shan Ngui; Yi-Wen Huang; Shao-Chi Hung; Shih-Han Huang; Chieh-Ju Wen; Yi-An Chang; Hsing-Chen Wu; Hsiu-Chuan Chan; Mei-Lin Chan; Liang-Yin Ke; Hua-Chen Chan (Molecular Biology Reports, 2026)

Seasonal differences in soil carbon stability along a Spartina alterniflora invasion chronosequence in the Yancheng coastal wetlands of China - Chen Liang; Lei Wang; Huan-Ju Wang; Shao-Yang Yang; Ai-Yun Song; Shou-Cai Wei; Lin-Shui Dong (CATENA, 2026)

Exosomal TGFBI promotes malignant progression of melanoma by regulating the FN1 signaling pathway - Yongliang Ge; Jingya Qiao; Lingling Ju; Lin Chen; Songnian Gao (Tissue and Cell, 2026)

Epitaxial high-entropy relaxor ferroelectric films for flexible piezoelectric sensors and MEMS - Yu-En Pan; Yu-Hao Tu; Li-Hui Tsao; Yu-Ju Lin; Sheng-Yao Hung; Yi-Chun Chen; Mengyao Xiao; Qibin Zeng; Huajun Liu; Chengkuo Lee; Ying-Hao Chu (Chemical Engineering Journal, 2026)

Electroacupuncture-induced gut microbiota alterations correlate with FXR/FGF15 activation and metabolic improvement in hyperlipidemic rats - Huan Wu; Li Zhou; Wei Lin; Hong-xing Zhang; Zhao-qing Zhang; Xiao-fei Wang; Shi-ru Ju; Zhi-gang Liu; Fei Hu (Advances in Traditional Medicine, 2026)

Mechanism-anchored ecological risk assessment of phthalates in coastal waters: Bridging environmental fate and molecular toxicity via an AOP framework - Shao-Yang Bu; Li-Ju Tan; Yan-Shan Chen; Kun Lin; Jiang-Tao Wang (Marine Pollution Bulletin, 2026)

Chondroitin sulfate: an environmentally friendly immune inducer enhanceing plant resistance to potato virus X and tobacco mosaic virus - Cui-Hong Hao; Wei Xu; Tian-Qi Liang; Yun-Mei Li; Yi-Lin Guan; Ru-Xin Li; Dan-Ya Ju; Chun-E Peng; Li-Zeng Peng; Qing-Bin Wang (Physiological and Molecular Plant Pathology, 2026)

Photo-assisted catalytic oxidation using PBA-derived ZnCo oxides in a H₂O₂ system for organic pollutant removal - Jia-Yin Lin; Yun-Ju Lai; Ying-hua Lai; Ta Cong Khiem; Nai-Wen Tsao; Yu-Chih Tsai (Journal of Water Process Engineering, 2026)

Corrigendum to “Susceptibility of Spodoptera frugiperda to novel insecticides and detection of known target-site mutations following invasion of Taiwan” [J. Asia-Pac. Entomol. 29(3) (2026)102584] - Hung-Ming Chao; Wen-Jer Wu; Li Lin; Hurng-Yi Wang; Ju-Chun Hsu (Journal of Asia-Pacific Entomology, 2026)

Susceptibility of Spodoptera frugiperda to novel insecticides and detection of known target-site mutations following invasion of Taiwan - Hung-Ming Chao; Wen-Jer Wu; Li Lin; Hurng-Yi Wang; Ju-Chun Hsu (Journal of Asia-Pacific Entomology, 2026)

Iron isotope evidence for rapid marine euxinia driven by volcanic Fe-C-S cycles during the end-Permian mass extinction - Qi Ju; Yi-bo Lin; Hua Zhang; Thomas J. Algeo; Shu-zhong Shen; Feifei Zhang (Geochimica et Cosmochimica Acta, 2026)

Fractionation-guided identification of an active polysaccharide fraction from the brown alga Scytosiphon lomentaria with anti-Vibrio harveyi activity and protective effects in shrimp - Su Liu; Hao Ju; Fei Liu; Xiaowei Song; Zijie Liu; Wancui Xie; Lin Song; Yi Gao (Food Bioscience, 2026)

The plastisphere: from microbial pollution to biodegradable solution - Wenfang Lin; Kai Yang; Tao Lu; Xiaoxi Kang; Xinyu Xing; Ewa Korzeniewska; Natalia P. Ivleva; Feng Ju; Haifeng Qian; Li Cui; Yong-guan Zhu (ENGINEERING Environment, 2026)
Microplastic pollution is threatening planetary health and sustainable development. The microbiota colonizing microplastic surfaces, termed the plastisphere, has emerged as artificial niches that harbor both microbial risks and novel biodegradation potential. However, these two aspects of the plastisphere have often been investigated in isolation. In this review, we first elaborate on how microplastics act as vectors in facilitating the enrichment and dissemination of pathogens, antibiotic resistance genes (ARGs), and even virus, thereby causing serious microbial and ecological risks, and eventually impacting human health. To address the potential risks, the key plastic-degrading resources, the underlying mechanisms, and recent advances in biodegradation technologies are synthesized. Given the dual roles of plastisphere microbes, we therefore propose a two-dimensional screening framework to identify safer and more efficient degraders. This review aims to guide the selection or synthesis of safe and highly efficient degrading microbial consortia, thereby providing sustainable and eco-friendly strategies for mitigating plastic pollution.

Climate change reshapes the dominant drivers of endorheic lakes on the Qinghai-Tibet Plateau - Hui Lin; Xuegao Chen; Nan Xu; Qin Ju; Jingcai Wang; Huanghe Gu; Tongqing Shen; Zhongxiang Wang; Xingrong Si; Jinguo Wang; Zhongbo Yu (Global and Planetary Change, 2026)

Stage-dependent aroma evolution of Liupao tea during long-term storage revealed by molecular sensory science - Lianqing Wang; Yuelan Pang; Ju Zhou; Meihui Huang; Zhichao Lin; Jing Wang; Hengbin Yao; Guohe Chen; Xuexue Zheng; Silei Bai; Jianan Huang; Zhonghua Liu; et al. (Food Chemistry, 2026)

Reaction-generated secondary phase advances electronic-phonon decoupling and boosted mechanical performance in Bi0.42Sb1.58Te3 alloys - Yi-lin Liu; Hao Liang; Chong-Yu Wang; Jiang-Hu Yu; Kang Yue; Qian Deng; Ju Rong; Jing Feng; Zhen-Hua Ge (Chemical Engineering Journal, 2026)

Plant–soil feedback persists beyond host death to shape density-dependent plant competition - Ching-Lin Huang; Joe Wan; Shuo Wei; Chia-Hao Chang-Yang; Po-Ju Ke (Plant and Soil, 2026)

Enhanced Monosaccharide Profile and Anti-Alcoholic Liver Injury Activity in the Liquid Fermentation of Ecklonia kurome by Inonotus hispidus - Baohong Wei; Xue Yang; Jia Liu; Wanghua Bi; Shaoping Wang; Shuman Hu; Xiaoqing Ma; Wenzhe Yang; Changyun Wang; Lin Ju; Huashi Guan (Journal of Ocean University of China, 2026)

Enzymatic synthesis of a new and bioactive dihydrochalcone: 3,4-dihydroxy-2′,6′-dimethoxy dihydrochalcone - Te-Sheng Chang; Jiumn-Yih Wu; Hsiou-Yu Ding; Tzi-Yuan Wang; Guan-Cheng Liu; Min-Lin Wang; Huei-Ju Ting (Natural Product Research, 2026)

Sensitivity of urban green space disparity assessment to NDVI data sources, acquisition timing, and alternative metrics - Jinyu Kong; Yang Ju; Iryna Dronova; Ying Liang; Jian Lin; Qin Ma (Urban Forestry & Urban Greening, 2026)

Targeted metabolomics analysis for discriminating geographical origin of Chardonnay grape and wine at sub-regions in China's Ningxia: Terroir effect - Xiaofeng Yue; Yang Zhang; Xinran Bai; Bo-chen Liu; Yu-lin Fang; Yan-lun Ju (Food Research International, 2026)

Heteronemin suppresses chemoresistant oral squamous cell carcinoma cells through ROS-mediated apoptosis and cuproptosis-associated mitochondrial stress - Chiung-Wei Huang; Fan-Li Lin; Chun-Feng Chang; Hsiao-Hsuan Huang; Wan-Ju Wu; Hui-Min Chang; Mei-Ying Lin; Jue-Liang Hsu; Shih-Ya Hung; Chien Hsing Lee (Apoptosis, 2026)

SYVN1-provoked RASA1 ubiquitination promotes pulmonary inflammation in chronic obstructive pulmonary disease - Ju-Hong Wu; Yi-Cheng Ma; Yu-Qi Wang; Hai-Long Miao; Meng-Xue Liu; Dong-Xu Hua; Min-Min Tang; Tian-Rui Sui; Zhi-Yong Wu; Yu Wang; Jin Yang; Hui Zhao; et al. (Inflammation Research, 2026)

Role of cholecystokinin (CCK) in reproductive regulation of female mandarin fish (Siniperca chuatsi) - Shuang Liu; Chongwei Wang; Yuting Wang; Chaowei Li; Jinmeng Teng; Suhan Peng; Jiaqi Lin; Jin Zhang; Haoran Lin; Linqiang Han; Ju Hu; Shuisheng Li; et al. (Aquaculture, 2026)

Multi-source isotopic tracing reveals meltwater runoff processes and environmental responses in the Yarlung Tsangpo River Basin - Zijun Zhang; Xuegao Chen; Hui Lin; Tongqing Shen; Qin Ju; Shiqin Xu; Ningpeng Dong; Peng Yi; Peng Chen; Naifeng Zhang; Yong Huang; Jinguo Wang; et al. (Journal of Hydrology, 2026)

Genesis of copper-deficient skarn iron deposits in the North China Craton: Insights from apatite and whole-rock geochemistry - Jun-Wu Zhang; Lin Li; Ju-Quan Zhang; Fang-Yue Wang; Xian Liang (Journal of Geochemical Exploration, 2026)

Effects of exogenous N-acyl-homoserine lactones on biofilm formation by denitrifying bacteria and denitrification start-up in sequencing batch biofilm reactors - Zhi-fei Li; Meng-yuan Yu; Jun-lin Li; Jun Xie; Xiang-ju Cheng; Wang-bao Gong; Kai Zhang; Guang-jun Wang; Yun Xia; Wen-ping Xie; Quan-fa Zhong; Hong-yan Li; et al. (Journal of Environmental Chemical Engineering, 2026)

Engineering a siderophore-macrolide conjugate via Trojan horse strategy for targeting Pseudomonas aeruginosa and related resistant pathogens - Chun-Yan Zhang; Wei-Min Chen; Guo-Bin Yang; Jing-Hua Wei; Zu-Ju Liang; Xi-Bing Hu; Ping Lan; Jing Lin; Jun Liu (Chemical Engineering Journal, 2026)

Divergent response of surface and deep soil nitrogen mineralization to nitrogen and phosphorus additions in a subtropical forest - Lige Zhang; Zi-Kai Liu; Shengsheng Jin; Luhong Zhou; Yongxin Lin; Shengjing Shi; Ju-Pei Shen (Soil Ecology Letters, 2026)

Dang-Gui-Bu-Xue-Tang triggers GM-CSF and IL-4 secretion corporated with increased amount of Immunoglobulins - Sheng-Teng Huang; Jia-Hau Yen; Yu-Chun Lin; Ming-Ching Kao; Chia-Ju Chuang; Shu-Tuan Chiang; Te-Mao Li (Advances in Traditional Medicine, 2026)

Characteristics of structural superimposed halo at the Jiawula Ag-Pb-Zn deposit, Inner Mongolia, China and its significance for exploration - Xin-yu Gao; Gui-yuan Sun; Kang Wang; Wei Zhang; Zhi-ping Li; Wen-ju Li; Jiang Wei; Lin Yang; Hong-zhe Xie; Zi-wen Yang; Chao Ma (Journal of Geochemical Exploration, 2026)

Inspired by facial masks: A nanocomposite fresh-keeping paper with moisturizing and antibacterial activities for fruit and vegetable preservation - Lin Zhang; Qingli Yang; Changjian Li; Mi Li; Jian Ju (Chemical Engineering Journal, 2026)

Pencil-drawn paper-based portable photoelectrochemical immunoassay of carbohydrate antigen 19-9 based on TiO2 hollow cube homogeneous junctions - Qinyan Chen; Qiong Lin; Yibin Zeng; Haining Li; Xiao Han; Dianping Tang; Gaoda Ju (Analytica Chimica Acta, 2026)

Vegetation in Central Asia is more sensitive to soil moisture stress than to precipitation and vapor pressure deficit stresses - Hongwu Liang; Guli Jiapaer; Cun Chang; Tao Yu; Liancheng Zhang; Pingping Feng; Kaixiong Lin; Tongwei Ju; Xiapeng Jiang; Philippe De Maeyer; Tim Van de Voorde (Agricultural and Forest Meteorology, 2026)

Machine Learning Approaches for Probabilistic Prediction of Coastal Freak Waves - Dong-Jiing Doong; Wei-Cheng Chen; Fan-Ju Lin; Chi Pan; Cheng-Han Tsai (Journal of Marine Science and Engineering, 2026)
Coastal freak waves (CFWs) are sudden and hazardous wave events that occur near shorelines and can pose serious threats to coastal visitors and infrastructure. Due to the complex interactions among coastal bathymetry, wave dynamics, and environmental conditions, the mechanisms governing CFW formation remain poorly understood, making reliable prediction difficult. This study investigates the feasibility of applying machine learning techniques to predict CFW occurrences using observational environmental data. Three machine learning algorithms, the Random Forest (RF), Support Vector Machine (SVM), and Artificial Neural Network (ANN), were developed to generate probability-based predictions of CFW events. Environmental variables derived from buoy observations, including wave characteristics, wind conditions, swell parameters, wave grouping indicators, and nonlinear wave interaction indices, were used as model inputs. Hyperparameters were optimized using grid search combined with k-fold cross-validation. The results show that all three models achieved comparable predictive performance, with AUC values close to 0.80 and overall prediction accuracy around 74%. The ANN model achieved the highest recall, indicating strong capability in detecting CFW events, while the RF and SVM models showed more balanced precision and recall. Analysis of high-probability prediction events suggests that CFW occurrences are associated with swell-dominated conditions, strong wave grouping behavior, and enhanced nonlinear wave interactions. These results demonstrate that machine learning provides a promising framework for probabilistic prediction of coastal freak waves and has potential applications in coastal hazard assessment and early warning systems.

Nitrogen-removal collapse and recovery: Integrative meta-omics insights into seasonal microbiome dynamics and cold-adaptive mechanisms in a full-scale activated sludge system - Limin Lin; Xinyu Zhu; Xiaoxing Lin; Ze Zhao; Hui Wang; Huizhen Yan; Feng Ju (Water Research, 2026)

Phytochrome-interacting factors (PIFs): Integrating phytohormone signals at the nexus of development and stress adaptation - Jiale Yuan; Ruiyun Wang; Xifeng Ju; Fang Lin (Journal of Plant Physiology, 2026)

Corrigendum to “Effect of BmPriL on the development of silk glands in silkworm” [J. Insect Physiol. 170 (2026) 104971] - HuaiRong Lin; Nuo Chen; Xiaohan Jiang; Shuxin Qiu; Niewang Ju; Qingyou Xia; Liang Jiang; Huizhen Guo (Journal of Insect Physiology, 2026)

Effect of BmPriL on the development of silk glands in silkworm - HuaiRong Lin; Nuo Chen; Xiaohan Jiang; Shuxin Qiu; Niewang Ju; Qingyou Xia; Liang Jiang; Huizhen Guo (Journal of Insect Physiology, 2026)

Laminar nanofiltration composite membranes based on two-dimensional aluminum-tetrakis(4-carboxyphenyl)porphyrin (Al-TCPP) nanosheets for efficient dye/salt wastewater treatment - Shao-Ju Lu; Chun-Po Hu; Chien-Chieh Hu; Chia-Her Lin; Wei-Song Hung; Kueir-Rarn Lee; Juin-Yih Lai (Journal of Environmental Chemical Engineering, 2026)

Climate change intensifies carbon emissions from the Earth's Third Pole: Projected trajectories of soil and ecosystem respiration - Tongqing Shen; Zhongbo Yu; Qin Ju; Junliang Jin; Guoqing Wang; Yanli Liu; Chunming Hu; Shixuan Lyu; Hui Lin; Xinrong Si; Feng Yan (Global and Planetary Change, 2026)

Linkage-resolved profiling of isomalto-oligosaccharides using porous graphitic carbon liquid chromatography–orbitrap tandem mass spectrometry - Chih-Chieh Lin; Meng-Jui Lin; Ju-Hua Chou; Pei-Yin Lin; Ting-Jang Lu (Food Chemistry, 2026)

Corrigendum to “AI-driven process-tolerant BioFET sensing model for precise biliary atresia diagnosis of infants with a single drop of blood” [Chem. Eng. J. (2026), volume 531, 1 March 2026, 173939] - Chia-Kai Lin; Chi-Ming Ku; Chia-Che Wu; Yi-Fang Wu; Huey-Ling Chen; Yueh-Ju Hou; Arnab Pal; Zong-Hong Lin; Chee-Seng Lee; Tzong-Rong Ger; Yu-Lin Wang (Chemical Engineering Journal, 2026)

Genome-wide characterization of the TCP family in Lagerstroemia and functional analysis of LfiTCP12 uncover its role in shoot branching promotion - Yan Xu; Ye Zhang; Chengzhi Li; Ruixia Yin; Hang Lin; Yu Zuo; Xin Huang; Bo Qin; Yiqian Ju (Plant Cell Reports, 2026)

A national-scale early detection and rapid response (EDRR) to invasive cane toads (Rhinella marina) in Taiwan - Yung-Chih Lai; Chun-Fu Lin; Li-Mien Tseng; Cheng-En Li; Jia-Han Lee; Jou-Yun Chen; Ming-Chih Wang; Chun-Hung Lai; Yueh-Feng Chen; Chun-Lin Ho; Wei-Chun Cheng; Yi-Ju Yang (Biological Invasions, 2026)

Evaluation of the effectiveness of indigenous entomopathogenic fungi for controlling chilli thrips (Scirtothrips dorsalis Hood) in blueberry under greenhouse conditions - Hsin-Yu Lin; Yi-Ju Chen; Kusum Mushyakhwo; Chin-Mu Chen; Yu-Shin Nai (BioControl, 2026)

Nickel refining fumes activate glutamine metabolism via the HIF‐1α/Notch pathway to drive epithelial-mesenchymal transition in Beas‐2B cells - Qian-Qian Sun; Han-Nong Yu; Rui-Ze Wu; Bo Zhang; Wen-Xue Yao; Wei-Yang Liu; Jia Han; Li-Yan Ju; Yu-Lin Pan; Yong-Hui Wu (Toxicology, 2026)

Inhibitory activity of dehulled adlay extrudate against ethanol-induced gastric mucosal injury and stability tests of active indicative components - Ming-Yi Lee; Shih-Min Hsia; Ching-I Lin; Yu-Chia Chang; Yi-Hsiang Liang; Lu-Chi Chan; Ju-Tsui Lin; Yi-Fen Chiang; Wei-Chih Sun; Cheng-Pei Chung (Journal of Cereal Science, 2026)

Boosting ammonia-fed solid oxide fuel cell performance via high-entropy alloy anode surface modification - Nasima Khatun; Cheng-Ju Lin; Jia-You Lin; Sridharan Balu; Shi-Shin Yang; Sea-Fue Wang; Thomas C.-K. Yang (Fuel, 2026)

AI-driven process-tolerant BioFET sensing model for precise biliary atresia diagnosis of infants with a single drop of blood - Chia-Kai Lin; Chi-Ming Ku; Chia-Che Wu; Yi-Fang Wu; Heuy-Ling Chen; Yueh-Ju Hou; Arnab Pal; Zong-Hong Lin; Chee-Seng Lee; Tzong-Rong Ger; Yu-Lin Wang (Chemical Engineering Journal, 2026)

Cytoplasmic-nuclear remote suppression of c-MYC induces cell cycle arrest and enhances radiotherapy sensitivity in liver cancer via biohybrid platelets - Lin Xiao; Fei Ge; Qinyu Ji; Rui Ji; Yan Wang; Shaoqing Ju; Ming Cui; Donglin Xia; Rongrong Jing (Chemical Engineering Journal, 2026)

Untargeted lipidomic profiling reveals the effect of hexabromocyclododecane exposure on a branching coral - Chuan-Ho Tang; Ting-Ju Liu; Ching-Yu Lin; Hsing-Hui Li (Aquatic Toxicology, 2026)

Clostridium butyricum Promotes Bone Remodeling by Activating Inflammatory Genes in Mice - Yanxin Jia; Longfei Xu; Zijing Ju; Mengze Song; Yonghao Zhou; Bin Li; Fang Wang; Hai Lin; Shuhong Sun; Haifang Li (Probiotics and Antimicrobial Proteins, 2026)

Coupled effects of straw return practices on soil microbial functional potential and agricultural productivity in Semi-Arid Region - Rui-Zhi Liu; Xiao-Ya Zhao; Li-Jie Wang; Xing Zhang; Shu‑Ping Hu; Ju‑Lin Gao; Xiao‑Fang Yu; Qinggeer Borjigin (Plant and Soil, 2026)

The safety of rituximab in pediatric nephrotic syndrome patients: a pharmacovigilance study of the FAERS database - Yanfeng Si; Fang Sun; Xu Wang; Xing Zhang; Rufeng Lin; Jiahua Ju; Yanqun Sun (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Soybean Hyperspectral Leaf Area Index (LAI) Estimation Based On Soil-vegetation Separation Algorithm and Derivative Spectroscopy - Nai-ning Zhong; Yu-lin Liu; Yi-zheng Zhao; Yi-xuan Mei; Hao-lin Shen; Xin-Zhou Lei; Yu-ning Wu; Juan-li Ju; Youzhen Xiang (Journal of Soil Science and Plant Nutrition, 2026)

Epidemiological characteristics of Chlamydial infection in hospitalized children in China: A nationwide retrospective study - Huiwen Zheng; Xinyu Wang; Xirong Wu; Yajie Guo; Feina Li; Jing Xiao; Hui Qi; Weiwei Jiao; Guoshuang Feng; Ju Yin; Lin Sun (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Intrinsic capacity across the adult lifespan in China: baseline analysis from the nationwide longitudinal PENG ZU cohort - Ju Cui; Yujia Gu; Jing Pang; Huafang Gao; Li-Qun Zhang; Xiaolan Wu; Junwu Dang; Juan Li; Xinyi Zhu; Senlin Luo; Zhao Wang; Fuyi Tu; et al. (GeroScience, 2026)

Captive breeding and early development of tank-reared lyretail anthias Pseudanthias squamipinnis (Peters, 1855): Assessments of hatching success, larval survival, and ontogeny - Ting-Chan Chou; Ang Lu; Yi-Yang Lin; Cheng-Chieh Wu; Hei-Wan Wong; Ho-Fai Yik; Bo-Kai Liao; Hong-Yi Gong; Yen-Ju Pan (Aquaculture, 2026)

Dual-phase engineered hierarchical CoP enables dynamic reconstruction and multimetallic synergy for superior oxygen evolution - Chunmei Ni; Xuena Gao; Huimin Yang; Jianguo Dong; Ju Wang; Changchun He; Zhao Li; Hui Xu; Lin Tian (Fuel, 2026)

Highly linear bionic strain decoupling sensor mediated by curved surface stress - Xueping Zhang; Junqiu Zhang; Jiachao Wu; Yu Chen; Xueyang Li; Wenjie Yu; Xiancun Meng; Guilin Li; Lina Ju; Bo Li; Tao Sun; Zhiwu Han; et al. (Chemical Engineering Journal, 2026)

The O-acetylation on phage tail-spike protein digested penta-saccharide from Acinetobacter baumannii SK44 plays a critical role in triggering pro-inflammatory immune response - Tzu-Yin Huang; Yen-Ju Yang; Boh-Woon Tay; Chun-Ting Lin; Shih-Hsiung Wu; I-Ming Lee (Carbohydrate Polymers, 2026)

Spatio-temporal dynamics of fish assemblages at an offshore wind farm and a comparison with mature artificial reefs - Kwang Tsao Shao; Ching Han Chang; Ching Yi Chen; Lin Tai Ho; Yi Ta Shao; Hsin-Chieh Chiang; Wei-Ning Lee; Hsien Ju Tsai; Tien-Yu Huang; Chun-Yu Chang (Frontiers in Marine Science, 2026)
Introduction Offshore wind farms (OWFs) are vital for sustainable energy. The underwater foundations of those wind turbines provide a complex structure that creates new habitats and attracts fishes. However, whether OWFs had the same ecological function as purpose-built artificial reef (AR) and how they alter the original fish community remain unclear. Methods To evaluate the spatial and temporal variations in fish assemblages, we conducted a multi-part investigation at the Formosa Wind Farm, located off the coast of Miaoli County, Taiwan. Temporal changes were assessed through SCUBA surveys at turbine foundations in 2017, 2018, and 2025, with the 2025 data allowing for a direct comparison with the nearby existing artificial reefs. To assess spatial effects, pole-and-line surveys were conducted from Apr to Oct in 2024 and 2025 at varying distances from the turbines. Results Our investigation documented 86 species of reef-associated fishes exclusively within 50 m of turbine foundations; none were caught in the surrounding sandy areas or documented in pervious fishery records. The results demonstrated that fish assemblages around the turbine piles changed successively over the years. Although the species composition in 2025 differed between the OWF and the established AR sites, key ecological metrics such as species richness, diversity, and trophic structures showed no significant differences. Discussion These findings demonstrated that the underwater structure of offshore wind turbines can function as AR, creating novel reef habitats and supporting reef-associated fish community within a finite spatial extent. Overall, OWFs may provide ecological benefits in addition to renewable energy, highlighting their potential role in balancing energy development with marine conservation.

Spermidine carbon quantum dots as an alternative antimicrobial agent for hatcheries rearing Pacific white shrimp (Litopenaeus vannamei) - Hung-Yun Lin; Han-Tso Lin; Yun-Ru Chiang; Ya-Yun Lu; James Pan; Hou-Ju Lin; Wan-Ching Kuo; Han-Jia Lin; Han-You Lin (Aquaculture, 2026)

Decadal variations in the northern boundary of permafrost in the Xidatan region of the Qinghai-Xizang Plateau: Insights from InSAR and field monitoring - Ju Xin; Luo Jing; Niu Fujun; Yu Fan; Ding Zekun; Yin Guoan; Lin Zhanju; Gao Zeyong (Cold Regions Science and Technology, 2026)

Oroxin A suppresses non-small cell lung cancer via the HSP90AA1/AKT signaling pathway - Mingxiao Wang; Yong Zhang; Ruoyang Liu; Juan Lin; Tengfei Wang; Huijun Dong; Ju Yang; Xiuyuan Li; Dehai Yu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

3-n-Butylphthalide Protects SH-SY5Y Cells from Ferroptosis by Inhibiting ACSL4-Mediated Lipid Peroxidation - Huanhuan Wei; Yiyin Zhang; Qianqian Ju; Bolin Lian; Tong Gao; Haiqin Duan; Xiang Yin; Yongqi Lin; Jianhong Shen; Qiuhong Ji; Cheng Sun; Lihua Shen (Molecular Neurobiology, 2026)

STAT3 Signaling Mediates Agomelatine Restoration of Prefrontal Cortex Synaptic Plasticity in Chronic Social Defeat Stress Mice - Chi-Wei Lee; Han-Fang Wu; Hsin-Ju Yen; Lun-De Liao; Wei-Chang Mao; Hsun-Shuo Chang; Yih-Fung Chen; Chia-Hsien Lin; Cheng-Ta Li; Hui-Ching Lin (Molecular Neurobiology, 2026)
Major depressive disorder (MDD) is a major public health issue worldwide. It not only causes an increased socio-economic burden, but also negatively affects personal lives. It has been shown that depression leads to impairments in synaptic plasticity, such as impaired long-term potentiation (LTP) in the prefrontal cortex (PFC). A recent study reported that administration of agomelatine, a melatonin receptor agonist and 5-hydroxytryptamine (5-HT) 2C antagonist, which may be involved in synaptic functions, for 1 week has a rapid antidepressive effect. Moreover, the mechanism of Glycogen synthase kinase 3β (GSK3β), regulated by signal transducer and activator of transcription 3 (STAT3), may play an important role in the synapse-related pathological mechanisms of depression. Hence, we used chronic social defeat stress (CSDS) as an animal model of depression, to investigate whether synaptic plasticity impairment in depression, improved by agomelatine, is mediated through the STAT3 mechanism. The results showed that depressive-like behaviors were reversed after 1 week of agomelatine treatment. Moreover, the impairment of LTP and alteration of spine density were reversed by agomelatine in the PFC. We further applied AG490, an inhibitor of STAT3, to demonstrate that the therapeutic mechanism of agomelatine improves synaptic plasticity through STAT3-regulated phosphorylation of GSK3β. Taken together, these results demonstrated that STAT3-regulated downstream molecules are potential therapeutic targets for the rapid action of antidepressants.

Oral Administrations of Short-Chain Fatty Acids or Probiotics Extend the Survival Times and Mitigate the Neuropathological Damages in the Scrapie-Infected Hamsters - Yuan Wang; Dong-Lin Liang; Run-Dong Cao; Ruhan A.; Jia-Feng Zeng; Bing Xu; Ju-Zheng Li; Wei-Wei Zhang; Li-Ping Gao; Kang Xiao; Xiao-Ping Dong; Qi Shi (Molecular Neurobiology, 2026)

Emerging trends and clinical challenges in AI-enhanced emotion diagnosis using physiological data - Ying-Ying Tsai; Guan-Lin Wu; Yu-Jie Chen; Yen-Feng Lin; Ju-Yu Wu; Ching-Han Hsu; Lun-De Liao (Medical & Biological Engineering & Computing, 2026)

Widespread weakening of soil-atmosphere thermal coupling and its response to climate warming on the Qinghai-Tibetan plateau - Guoan Yin; Xin Ju; Fujun Niu; Zhanju Lin; Jing Luo; Zeyong Gao; Hongye Yan; Yanhe Wang; Weiheng Ni (Agricultural and Forest Meteorology, 2026)

Tracking mitigation and expression patterns of the antibiotic resistome during full-scale livestock wastewater treatment: Comparison between summer and winter conditions - Xinyu Zhu; Limin Lin; Feng Ju (Water Research, 2025)

Anti-diabetic quinolone alkaloids from the fruits of Tetradium ruticarpum - Chun-Lin Zhao; Kai-Wen Kang; Zhi-Cheng Su; Hong-Yan Mu; Hui-Shan Guo; Hui-Zhen Chen; Ya-Ting Chen; Jing-Wei Jin; Ju-Cai Xu; Hong-Guang Li; Li-She Gan (Phytochemistry Letters, 2025)

Labdane-type diterpenoids from Hypoestes phyllostachya inhibit pancreatic cancer stem cells - Tong Yan; Lin-Fen Ding; Ya Chen; Guo-Xian Hu; Lu Qu; Ming Hu; Ya-Xuan Ma; Rong-Qing Yuan; Lin Jia; Mei-Ju Zhao; Liu-Dong Song; Jia Su; et al. (Phytochemistry, 2025)

Hydrogeochemical characteristics and the monitoring from 2020 to 2023 of hot spring waters in Tatun Volcanic Group, Taiwan - Ju-lien Pi; Hsueh-Yu Lu; Hsiao-Fen Lee; Hung-Chun Chao; Chen-Feng You; Tsung-Ren Peng; Raymond Patrick R. Maximo; Chia-Tai Wu; Ya-Wen Wu; Chung Fang; Cheng-Horng Lin (Journal of Asian Earth Sciences, 2025)

Rapid and sensitive on-site detection of peach (Prunus persica) species in fruit juices using a RAA-CRISPR/Cas12a approach - Lin Wang; Ran-Ran Xing; Xiao-Ke Liang; Yao-Xian Yu; Qiu-Ju Yi; Si-Yuan Lu; Ting-Ting Deng; Jiu-Kai Zhang; Xu Wang; Ying Chen (Food Control, 2025)

Detection of Marteilioides chungmuensis in cultured Portuguese oyster (Crassostrea angulata) in southern Taiwan - I-wen Chen; Chieh-Hao Wu; Yi-Pin Lu; Yu-Ju Lin (Fish & Shellfish Immunology, 2025)

Effect of the CuxNi1-xN bimetallic electrocatalyst on the ignition and combustion of electrically controlled solid propellants - Ziyang Han; Qiyang Wang; Huimin Nai; Haoyang Lu; Yingxue Ju; Jian Zhang; Debin Xia; Yulin Yang; Kaifeng Lin (Chemical Engineering Journal, 2025)

Novel self-assembled antimicrobial peptide Pardaxin hydrogel as a functional biomaterial for food packaging and preservation - Sanjay Prasad Selvaraj; Ju-Chun Chang; Karukuvelraja Raja; Jing-Ting Zhu; Prakash Kishore Hazam; Wen-Chun Lin; Jung-Ren Huang; Tsung-Lin Li; Jyh-Yih Chen (Chemical Engineering Journal, 2025)

Flexible bifunctional electrode with a record-breaking ΔE = 0.55 V for fast charging fiber zinc-air batteries - Long Jiang; Yumin Chen; Jing Zhou; Huangjian Chen; Yunzhan Ying; Shikun Liang; Yulong Wan; Shifan Zheng; Ju Lin; Yuyuan Yao; Lihua Gan; Lie Wang (Chemical Engineering Journal, 2025)

Drivers of protistan communities in a subtropical coastal wetland: roles of plant types and soil depths - Zi-Kai Liu; Lu Li; Bowen Huang; Luhong Zhou; Yongxin Lin; Ping Yang; Ju-Pei Shen; Weidong Chen (CATENA, 2025)

Pluvial flood warnings in a tidally influenced basin enhanced by rainfall–tide compound indicators: Taipei case study - Mei-Ying Lin; Wen-Yih Sun; Huei-Syuan Fu; Chih-Hsin Chang; Wei-Bo Chen; Chieh-Ju Wang; Hsuan-Wei Wang; Yi-Chiang Yu; Yen-Wei Li (Stochastic Environmental Research and Risk Assessment, 2025)

Synergistic effects and mechanism of recombinant viral vector-mediated STAT1 overexpression and STAT3 silencing on glioma U251 apoptosis - Xin-Long Hu; Hong Li; Guo-Dong Zhang; Chao Lin; Ping Huang; Xiu-Feng Chen; Fang Wan; Chang-Wu Dou; Hai-Tao Ju (Molecular Biology Reports, 2025)

Levonorgestrel-induced sex reversal in mandarin fish (Siniperca chuatsi): An effective protocol for all-female production and its aquaculture applications - Shiyan Liu; Jinmeng Teng; Suhan Peng; Shuang Liu; Jiaqi Lin; Long Chen; Ju Hu; Haoran Lin; Caiyun Sun; Shuisheng Li; Songlin Chen; Chong Han; et al. (Animal Reproduction Science, 2025)

Rhizosphere remediation of saline-alkali soils by Helianthus tuberosus: Linking microbial-metabolite synergies to carbon sequestration - Tianyun Shao; Yang Yue; Wenhan Dong; Jiayan Lin; Yilong Ma; Zhaosheng Zhou; Xiumei Gao; Hui Guo; Xiaohua Long; Ju zhao; Yu Zhang (Science of The Total Environment, 2025)

The dual role of organic carbon: Mitigation of nitrogen-induced soil acidification but amplification of greenhouse gas emissions - Lin Zhao; Qinghua Li; Yufang Lu; Hongmei Chen; Ju Min; Ren Fang Shen; Xue Qiang Zhao (Journal of Environmental Management, 2025)

A safe and high-precision detection method for hydrogen leakage analysis of underground gas storage based on stimulated Raman spectroscopy of micro-nanofiber - Xianjian Zou; Shoulin Jiang; Zixue Luo; Tongtao Wang; Feifan Chen; Jian Ju; Shaoqun Lin; Wei Jin; Jianhua Yin; Chunhe Yang (Fuel, 2025)

Prediction model of activated surface moving deformation in old coal mine goaf considering dynamic load - Yuanjiang Ju; Yan Lin; Chao Liu; Hasidere Tuerxunhazi (Bulletin of Engineering Geology and the Environment, 2025)

A finite-volume based physics-informed Fourier neural operator network for parametric learning of subsurface flow - Xia Yan; Jingqi Lin; Yafeng Ju; Qi Zhang; Zhao Zhang; Liming Zhang; Jun Yao; Kai Zhang (Advances in Water Resources, 2025)

Human adenovirus in Taiwan, 2019–2023 - Su-Lin Yang; Wan-Ju Tsai; Chung-Hao Li; Yu-Hsin Cheng; Shu-Wei Lin; Ming-Tsan Liu; Fang-Tzy Wu (Archives of Virology, 2025)

Recent advances in Pyrazolo[3,4-d]pyrimidine-based dual inhibitors in the treatment of cancers - Hanrui Jiang; Nan Li; Ruosong Qin; Siyu Lin; Xuelian Wang; Chunyan Li; Jiwei Shen; Ye Chen; Ju Liu; Shi Ding (Molecular Diversity, 2025)

Development of the immunopharmacognostic interventions on potentiating tumor recognition against prostate cancer - Tzu-Ting Su; Jun-Wei Lin; Shen-Chieh Wang; Tai-Yang Chen; Ju-I Chana; Pei-Wen Hsiaa; Hui-Ming Chen (Phytochemistry Letters, 2025)

Mechanistic insights into capacitive ion exchange for selective divalent ion removal using activated carbon electrodes - Ming-Han Tsai; Shu-Ju Chao; David Chiuni Wang; I-Hsuan Lin; Li-Ching Chung; Po-I Liu; Lap-Cuong Hua; Hung-Yi Huang; Chi-Chang Hu (Chemical Engineering Journal, 2025)

A strategy for enhancing mechanical properties of electrically controlled solid propellant via in-situ-induced microphase separation - Huimin Nai; Qiyang Wang; Yingxue Ju; Yangshun Ren; Jiahui Li; Jizeng Shang; Jian Zhang; Debin Xia; Ping Wang; Yulin Yang; Kaifeng Lin (Chemical Engineering Journal, 2025)

The Antimicrobial Peptide Tilapia Piscidin 4 Induced the Apoptosis of Bladder Cancer Through ERK/SIRT1/PGC-1α Signaling Pathway - Chun-Feng Chang; Po-Chih Chang; Yi-Chen Lee; Chieh-Yu Pan; Hui-Min Chang; Wan-Ju Wu; Mei-Ying Lin; Chung-Yi Chen; Zhi-Hong Wen; Chien-Hsing Lee (Probiotics and Antimicrobial Proteins, 2025)

Spatiotemporal dynamics of retrogressive thaw slumps on the Qinghai-Tibet Plateau: integrating UAV-LiDAR and GPR - Fan Yu; Jing Luo; Fujun Niu; Zhanju Lin; Bingyan Li; Yanhu Mu; Xin Ju; Minghao Liu; Guoan Yin; Zeyong Gao; Xiaolong Zhao; Chengming Zhang (Landslides, 2025)

Classification of HC, MCI, and AD Based on CT Using Deep Learning - Ing-Tsung Hsiao; Kun-Ju Lin; Chiung-Chih Chang; Hsuan-Ming Huang (Journal of Medical and Biological Engineering, 2025)

Unveiling Unusual Ecofunctional Traits of Endozoicomonas Species Through Comprehensive Comparative Genomics - Sim Lin Lim; Ching‐Hsiang Chin; Yu‐Jing Chiou; Ming‐Tsung Hsu; Pei‐Wen Chiang; Hsing‐Ju Chen; Yung‐Chi Tu; Wen‐Shyong Tzou; Sen‐Lin Tang (Environmental Microbiology, 2025)
Endozoicomonas is an omnipresent marine bacterial genus, associated with various marine organisms, that contributes to host health, nutrient cycling and disease resistance. Nonetheless, its genomic features remain poorly characterised due to a paucity of high‐quality genomes. In this study, we sequenced 5 novel Endozoicomonas strains and re‐sequenced 1 known strain to improve genomic resolution. By integrating these 6 high‐quality genomes with 31 qualified published genomes, our pan‐genomic analysis revealed variation in genetic traits among clades. Notably, Endozoicomonas lacks quorum‐sensing capabilities, suggesting resistance to quorum quenching mechanisms. It also lacks the capacity to synthesise and transport vitamin B12, indicating that it does not supply this nutrient to holobionts. Remarkably, Endozoicomonas genomes encode 92 identified giant proteins (15–65 kbp). These proteins cluster into three major groups associated with antimicrobial peptide synthesis, exotoxin production and cell adhesion. Additionally, we found that Endozoicomonas has acquired prophages from diverse sources via infection or other types of gene transfer. Notably, CRISPR‐Cas sequences suggest evolutionary trajectories independent of both prophage acquisition and phylogenetic lineage, implying potential geographic influences or environmental pressures. This study provides new insights into the genomic diversity of Endozoicomonas and its genetic adaptations to diverse hosts.

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Constructing Ni2P/CoP heterojunction with stable built-in electric field to boost overall water splitting at industrial current density - Tian Lin; Huimin Yang; Jianguo Dong; Chunmei Ni; Xuena Gao; Jing Li; Ju Wang; Xiaoyan He; Wenyi Tan; Ligang Feng; Zhao Li (Fuel, 2025)

Ratiometric photoelectrochemical aptasensor for ultrasensitive kanamycin detection based on superior photoactive high-entropy sulfide nanosheets coupling with dual-atom nanozyme inducing polarity switch - Jia-Lin Li; Li-Ping Mei; Ai-Jun Wang; Pei Song; Jiu-Ju Feng (Chemical Engineering Journal, 2025)

Spin-blockade effect of chiral multi-branch Au nanoparticles for mediating oxygen evolution reaction of electro-catalytic water splitting - Rui Tian; Lufei Huang; Ying Li; Dewei Zhang; Shenghong Ju; Baowen Zhou; Lin Yao (Chemical Engineering Journal, 2025)

Assessments of Water Quality in Tibetan Plateau Require Focus on Heavy-Metal Indicators: Evidence from the Lhasa River - Bingdan Jiang; Yiming Tang; Yinjie Zhang; Wenhui Ju; Aijun Lin (Water, Air, & Soil Pollution, 2025)

Screening of Antibiotic-Sensitive Lactic Acid Bacteria (LAB) Associated with the Gut of Penaeus Vannamei and its Application in Shrimp Farming - Yiwen Gu; Xiu Lin; Yanxu Lu; Shuguang Fang; Kun Hu; Xin Ju; Liangzhi Li; Zhi Chen (Current Microbiology, 2025)

A new illudane sesquiterpene from the edible fungus Pholiota nameko - Lian Yang; Huan Zhang; Shu-Hang He; Ju Xu; Xiao-Long Li; Fei-Xing Li; Dong-Mei Lin; Deng-Ji Lou; Xiao-Yan Yang (Natural Product Research, 2025)

YOLO-CMST: Towards accurate pineapple flowering induction using YOLO-based models with the Cross Multi-Style Translator - Kuang-Yueh Pan; Wan-Ju Lin; Jian-Wen Chen; Yi-Hong Lin (Computers and Electronics in Agriculture, 2025)

Host-mediated environmental microbiome recruitment by black soldier fly (Hermetia illucens) enhances waste biotransformation - Zhe Li; Yuchen Zhou; Lin Lv; Yinguang Long; Mengyao Dong; Qi Xiao; Xianyue Jia; Dechen Ju; Xiaowen Sun; Feng Huang; Minmin Cai; Jibin Zhang; et al. (Waste Management, 2025)

A symbiotic bacterium regulates the detoxification metabolism of deltamethrin in Aedes albopictus - Si-jia Deng; Lei Tu; Lin Li; Ju-ping Hu; Ju-lin Li; Jian-xia Tang; Mei-chun Zhang; Guo-ding Zhu; Jun Cao (Pesticide Biochemistry and Physiology, 2025)

SMART-assisted discovery of butenolides from the marine-derived Aspergillus sp. NBU4698 with multidrug resistance reversing and anti-inflammatory activity - Hang Zhao; Zhiyan Zhou; Fangjian Feng; Wei Yuan; Lixin Chen; C. Benjamin Naman; Zhiran Ju; Ziyi Zhou; Wenhan Lin; Shan He; Lijian Ding (Phytochemistry, 2025)

Passion fruit peel pectin improves glucose and lipid metabolism in high-fat diet-induced obesity through gut microbiota and insulin sensitivity regulation - Ying Ju; Liling Huang; Hailing Luo; Yongcai Huang; Xianya Huang; Ge Chen; Jie Gui; Shengli Lin; Xuzhou Liu; Liu Yang (Food Bioscience, 2025)

Novel xylanase activity and biofuel production in Lacrimispora xylanolytica isolated from termite guts symbionts - Chia-Chi Yang; Yu-Ju Lin; Fu-Shyan Wen (Bioresource Technology, 2025)

The Development of an Automatic Amyloid PET Quantification (AmPQ) Software with MR-based and MR-free Spatial Normalization - Shao-Yi Huang; Kun-Ju Lin; Zong-Jhe Lyu; Ing-Tsung Hsiao (Journal of Medical and Biological Engineering, 2025)

Long-term organic farming may prevent nitrate leaching by enhancing the abundance and co-occurrence of nasA-type nitrate assimilatory bacteria - Hui Han; Juan Du; Hanye Ju; Chunyu Wang; Yajuan Fu; Shuanghu Fan; Lin Wang; Xiaoqiang Hou; Qiuzhen Wang (Applied Soil Ecology, 2025)

The Evolution of the Order Siphonaptera Inferred from the First Mitogenome of the Family Pygiopsyllidae - Xiaoxia Lin; Ju Pu; Wenge Dong (Acta Parasitologica, 2025)

Deep learning reveals the relationship between vegetation and runoff in the Weihe River Basin on the Loess Plateau - Qin Ju; Wenjie Zhao; Tongqing Shen; Junliang Jin; Hui Lin; Xiaoni Liu; Peng Jiang; Jianhui Wei; Zhongbo Yu (Hydrological Sciences Journal, 2025)

Integrating organic amendments and enhanced efficiency fertilizers for sustainable rice production——A case study in a tropic paddy system - Tianjie Xie; Jinghua Li; Shengwei Lin; Xiaotang Ju; Tingyu Li (Journal of Cleaner Production, 2025)

Comparing tea-drinking experiences in virtual outdoor landscape restaurants with different levels of perceived environmental naturalness - Pei-Lun Sun; Yeqiang Kevin Lin; Po-Ju Chang (Landscape and Ecological Engineering, 2025)

Searching for neutrinoless double-beta decay of 136 Xe with PandaX-4T - Shu Zhang; Zihao Bo; Wei Chen; Xun Chen; Yunhua Chen; Zhaokan Cheng; Xiangyi Cui; Yingjie Fan; Deqing Fang; Zhixing Gao; Lisheng Geng; Karl Giboni; et al. (Science Bulletin, 2025)

A novel deacetylase inhibitor KLX suppresses liver fibrosis by deacetylating PPARγ through promoting ubiquitination-mediated HDAC1 degradation - Feng Zhang; Jinglun Song; Han Wu; Keying Lin; Chunlei Wang; Linghua Zeng; Xue Kong; Kunkun Zou; Hongtao Diao; Zhuo Wang; Wei Si; Weitao Jiang; et al. (Science China Life Sciences, 2025)

Microbiological Activity and Oxygen Availability Influence Arsenic Mobilization and Redox Transformation in an Arsenic-Rich Aquifer - Yu-Chen Su; Yu-Ju Chu; Chia-Cheng Wei; Chan-Wei Yu; Pei-Ling Yen; Yu-Hsuan Kuo; Ting-An Lin; Vivian Hsiu-Chuan Liao (Exposure and Health, 2025)

RNA-binding protein expression based machine learning model predicts metastasis and treatment outcome of testicular cancer - Lin-jian Mo; Hai-qi Liang; Zhen-yuan Yu; Yao-wen Liang; Chuan-xin Gu; Qiu-ju Wei; Qi-huan He; Fa-ye Wei; Ji-wen Cheng; Zeng-nan Mo (Genes & Genomics, 2025)

Monitoring of genetically modified crops in food products in Singapore - Yanwen Wang; Kung Ju Lin; Emily Huey Shyan Teo; Yong Quan Tan; Yuansheng Wu; Kern Rei Chng; Joanne Sheot Harn Chan; Li Kiang Tan (Food Control, 2025)

Enhanced selective sorption of Cu(II) from washing solution of fly ash using polyethyleneimine-crosslinked chitosan sorbents - Yu Gong; Zitao Lin; Jing Yang; Yongming Ju; Dorota Kołodyńska; Jie Liu; Xiaohan Shan; Yujie Wang; Yong Zhang; Weixin Li (Chemical Engineering Journal, 2025)

Nanoengineered cellulose for sustainable selective separation of precious metals from electronic waste - Roya Koshani; Shang-Lin Yeh; Mica L. Pitcher; Lucas Lawrence Franz; Mitchell Robert Davis; Min Ju Park; Said Khalifa Ahmed Al Qassabi; Joelson Patricio Manuel Alves; Younes Shekarian; Hevapathiranage Chandima Sudantha Subasinghe; Sarma V. Pisupati; Mohammad Rezaee; et al. (Chemical Engineering Journal, 2025)

Altered 3D genome reorganization mediates precocious myeloid differentiation of aged hematopoietic stem cells in inflammation - Xinyu Cui; Yu Dong; Qiang Zhan; Yixin Huang; Qianshu Zhu; Zihao Zhang; Guang Yang; Liping Wang; Shijun Shen; Jia Zhao; Zhiyi Lin; Jiatong Sun; et al. (Science China Life Sciences, 2025)

CTHRC1 expresses in cancer-associated fibroblasts and is associated with resistance to anti-androgen therapy in prostate cancer - Hai-qi Liang; Qi-huan He; Qiu-ju Wei; Qi-zhou Mo; Guang-lin Yang; Fa-ye Wei; Li-wei Wei; Yu-jian Li; Min Qin; Ji-wen Cheng (Genes & Genomics, 2025)

Temporal Dynamics of Genetic Diversity in Protected and Unprotected Wild Rice ( Oryza rufipogon ) Populations: Implications for Conservation - Zhi‐Zhou He; Wen‐Wen Shao; Olivier Honnay; Hui Liao; Hao Chen; Jing Liu; Shan‐Shan Dong; Ding Li; Guo‐Zhen Fan; Yao Zhao; Jun Rong; Yan Liu; et al. (Molecular Ecology, 2025)
Genetic diversity is vital for population survival, yet there is a paucity of studies focusing on the effectiveness of establishing protected areas for maintaining the population genetic diversity of threatened plant species. To evaluate the effectiveness of in situ conservation measures, we used simple sequence repeats (SSR) and single nucleotide polymorphisms (SNP) markers to monitor temporal dynamics in genetic diversity of the threatened wild rice Oryza rufipogon in both protected and unprotected populations in China between 2001 and 2020. Unprotected populations tended to have decreased census population sizes ( Nc ) compared to protected populations, although they both showed a reduction in effective population size ( Ne ). While allele diversity and expected heterozygosity remained stable, several populations, especially those without protection, exhibited a significant decrease in observed heterozygosity ( Ho ) and an increase in inbreeding ( F IS ). The level of genetic differentiation between populations did not change over time, but the number of private alleles increased and Ne varied in several populations, indicating the effects of genetic drift. Indicators for temporal trends in Ho , F IS , and Ne revealed that both protected and unprotected populations are facing warnings of declining genetic diversity, although some protected populations remain resilient, reflecting the genetic lag behind Nc change. Overall, these findings highlight the effectiveness of in situ conservation efforts in maintaining population size and genetic diversity, yet we also show the necessity of lasting population dynamics monitoring, using different genetic indicators.

Nationwide suspect screening of new psychoactive substances (NPSs) and other controlled substances in Taiwan wastewater using liquid chromatography–High resolution mass spectrometry (LC-HRMS) - Yuan-Chih Chen; Jen-Yi Hsu; Yung-Chieh Lin; Chiau-Jun Chu; Yen-Ping Lin; Yun-Ju Tsai; Pao-Chi Liao (Chemosphere, 2025)

Insight into selective removal of trace thallium (Tl(Ι)) by novel chitosan adsorbents encapsulating low-cost silicate mineral wastes - Yu Gong; Yujie Wang; Jing Yang; Yongxin Bing; Zifei Sun; Yongming Ju; Xiaochen Lin; Houhu Zhang; Zitao Lin; Weixin Li (Environmental Research, 2025)

Origins of the overestimated Indian Ocean dipole amplitude in current coupled climate models - Xiaoming Ju; Shangfeng Chen; Wen Chen; Renguang Wu; Lin Chen; Xin Cheng (Climate Dynamics, 2025)

Co-adsorption of methylene blue/Pb(II) from aqueous solutions using sulfonated mesoporous diatomite - Ali M. Abou-Elanwar; So Young Lee; Jeongkyun Yu; Jieun Kim; Chihyun Hwang; Hyungmin Park; Young-tai Noh; Ming Xie; Jiuyang Lin; Seong-Ju Park; Dong Han Seo; Youngjin Kim (Journal of Water Process Engineering, 2025)

Exploring the influence of PCB exposure on neonatal birth outcomes and neurobehavioral development after 15 years of prohibition - Tzu-Hsuen Yuan; Chun-Ju Tai; Cheng-Hsien Tsai; Jien-Wen Chien; Akifumi Eguchi; Chih-Yun Li; Ching-Wen Lin; Chisato Mori; Chang-Chuan Chan (Environmental Pollution, 2025)

Insufficient MIRO1 contributes to declined oocyte quality during reproductive aging - Zhen-Nan Pan; Hao-Lin Zhang; Kun-Huan Zhang; Jia-Qian Ju; Jing-Cai Liu; Shao-Chen Sun (Science China Life Sciences, 2025)

Interaction of microalgae, nitrogen and arsenic in a water environment co-polluted by nitrogen and arsenic: current knowledge and future perspectives - Youwen Li; Xinxin Zhao; Zhaoqi Zhong; Fanfan Ju; Hui Liu; Ning Lin; Xianghao Zha (Aquatic Ecology, 2025)

Protective effects of dietary protein against nitrite stress in grass carp (Ctenopharyngodon idella): A new perspective - Hong-Ju Liu; Xiao-Qiu Zhou; Pei Wu; Wei-Dan Jiang; Yang Liu; Hong-Mei Ren; Xiao-Wan Jin; Hai-Feng Mi; Min Dong; Lu Zhang; Lin Feng (Aquaculture, 2025)

Accelerated inverse urban design: A multi-objective optimization method to photovoltaic power generation potential, environmental performance and economic performance in urban blocks - Gaomei Li; Qiuguo He; Borong Lin; Minghao Wang; Xiaolei Ju; Shen Xu (Sustainable Cities and Society, 2025)

Methane Index and TEX86 values in cold seep sediments: Implications for paleo-environmental reconstructions - Sze Ling Ho; Yu-Shih Lin; Pei-Ling Wang; Tzu-Ting Chen; Pei-Ting Lee; Hui-Hsin Wang; Tzu-Jung Cheng; Yun-Ju Wang; Chih-Chieh Su; Min-Te Chen (Geochimica et Cosmochimica Acta, 2025)

The dissolved oxygen variation in seagrasses is influenced by DOC excretion and its associated microbes - Tzu-Hsuan Tu; En-Ju Lin; Chin-Chang Hung; Wen-Chen Chou; Yung-Yen Shih (Estuarine, Coastal and Shelf Science, 2025)

Digital transformation of mental health therapy by integrating digitalized cognitive behavioral therapy and eye movement desensitization and reprocessing - Ju-Yu Wu; Ying-Ying Tsai; Yu-Jie Chen; Fan-Chi Hsiao; Ching-Han Hsu; Yen-Feng Lin; Lun-De Liao (Medical & Biological Engineering & Computing, 2025)

Correction to: Resveratrol Mitigates Cerebral Ischemic Injury by Altering Levels of Trace Elements, Toxic Metal, Lipid Peroxidation, and Antioxidant Activity - Ju-Hai Ro; Chien-Chi Liu; Ming-Cheng Lin (Biological Trace Element Research, 2025)

Enhanced nano-LC-MS for analyzing dansylated oral cancer tissue metabolome dissolved in solvents with high elution strength - Ya-Ju Hsieh; Cheng-Yu Hung; Yi-Ting Chen; Yu-Tsun Lin; Kai-Ping Chang; Wei-Fan Chiang; Chih-Yen Chien; Chih-Ching Wu; Liang Li; Jau-Song Yu; Kun-Yi Chien (Analytica Chimica Acta, 2025)

Antimicrobial efficacy of carvacrol-loaded curdlan hydrogels for enhancing shelf-life in seafood packaging applications - Hong-Ting Victor Lin; Yi-Chi Yu; Shu-Han Yu; Yu-Chieh Chou; Hsuan-Ju Lin; Shella Permatasari Santoso; Shin-Ping Lin (International Journal of Food Microbiology, 2025)

Cost-Effectiveness Analysis of Nearly Zero-Carbon Office Buildings in Taiwan - Chia-Ju Yen; Hsien-Te Lin; Kuei-Peng Lee (Building and Environment, 2025)

Epigenetic Modifications as Novel Therapeutic Strategies of Cancer Chemoprevention by Phytochemicals - Hui-Hsia Hsieh; Min-Zhan Kuo; I-An Chen; Chien-Ju Lin; Victor Hsu; Wei-Chun HuangFu; Tien-Yuan Wu (Pharmaceutical Research, 2025)

Retraction Note: Micafungin exerts antitumor effect on breast cancer and osteosarcoma through preventing EMT in tumor cells in an USP7/AKT/GSK-3β pathway-dependent manner - Qian-Lin Wang; Li Wang; Qiong-Yu Li; Hui-Yin Li; Ling Lin; Dan Wei; Jin-Yun Xu; Xiu-Ju Luo (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Protective Effects of Antcin H Isolated from Antrodia cinnamomea Against Neuroinflammation in Huntington’s Disease via NLRP3 Inflammasome Inhibition - Yu-Jun Chang; Cheng-Hsu Chen; Yi-Chen Chen; Ming-Tse Wu; Ting-Yu Lin; Kuo-Feng Hua; Tz-Chuen Ju (Journal of Neuroimmune Pharmacology, 2024)

Potato Protein Hydrolysate (PPH902) treatment in adipocytes inhibits lipogenesis by activating AMPK - Yi-Ju Chen; Ching-Fang Chang; Rathinasamy Baskaran; Chih-Hung Liang; Hsin-Ning Kuo; Mosleh Mohammad Abomughaid; Wan-Teng Lin (South African Journal of Botany, 2024)

Lake responses and mechanisms to El Niño on the Tibetan Plateau using deep learning-based semantic segmentation - Hui Lin; Zhongbo Yu; Xuegao Chen; Huanghe Gu; Qin Ju; Tongqing Shen; Jingcai Wang (Journal of Hydrology, 2024)

An integrated solution of energy storage and CO2 reduction: Trans-critical CO2 energy storage system combining carbon capture with LNG cold energy - Liang Yin; Yonglin Ju; Qianguo Lin (Journal of Cleaner Production, 2024)

Response to “Letter to the Editors” regarding “A nationwide case-referent study on elevated risks of adenocarcinoma lung cancer by long-term PM2.5 exposure in Taiwan since 1997” - Wei-Chi Lin; Ruei-Hao Shie; Tzu-Hsuen Yuan; Chien-Hua Tseng; Chun-Ju Chiang; Wen-Chung Lee; Chang-Chuan Chan (Environmental Research, 2024)

Ru induced charge redistribution of MnO2 spheric nanozyme boosted hydrogen sulfide selective detection and cystathionine γ-lyase activity sensitive evaluation - Zhao Li; Xuan Zhang; Haorong Cheng; Zhongyuan Gu; Changchun He; Ju Wang; Xinxin Shi; Weidan Na; Tongxiang Li; Lin Tian (Chemical Engineering Journal, 2024)

From agricultural biomass to D form lactic acid in ton scale via strain engineering of Lactiplantibacillus pentosus - Chia-Chi Yang; Chia-Hau Chou; Gia-Luen Guo; Yu-Ju Lin; Fu-Shan Wen (Bioresource Technology, 2024)

Photo-transformation of biochar-derived dissolved organic matter and its binding with phenanthrene/9-phenanthrol: The role of functional group and pyrolysis temperature - Yifan Niu; Siyao Wang; Peng Gao; Xin Ren; Fangfang Li; Zhanpeng Liu; Lin Wang; Hongbo Peng; Shaohua Ju (Bioresource Technology, 2024)

Enhancing real-time PM2.5 forecasts: A hybrid approach of WRF-CMAQ model and CNN algorithm - Yi-Ju Lee; Fang-Yi Cheng; Hsiao-Chen Chien; Yuan-Chien Lin; Min-Te Sun (Atmospheric Environment, 2024)

Population pharmacokinetic analyses of pozelimab in patients with CD55-deficient protein-losing enteropathy (CHAPLE disease) - Kuan-Ju Lin; Jeanne Mendell; John D. Davis; Lutz O. Harnisch (Journal of Pharmacokinetics and Pharmacodynamics, 2024)

Early Cretaceous mafic dikes in the eastern North China Craton: implications for the effect of slab subduction on the mantle sources - Chao Li; Lin Li; Ju-Quan Zhang; M. Santosh; Sheng-Rong Li; Bowen Wei; Cong Li (International Geology Review, 2024)

Evaluating the embryotoxicity of benzophenone-based photoinitiators in stem cells and zebrafish embryos - Chen-Yi Weng; Tzu-Ching Chang; Jun-Yang Liou; Ju-Hsin Hsu; Chia-Chi Ho; Salim Arrokhman; Pinpin Lin (Toxicology, 2024)

Long-term effects of conventional cultivation on soil cation exchange capacity and base saturation in an arid desert region - Dengke Ma; Zhibin He; Wenzhi Zhao; Rui Li; Weihao Sun; Wen Wang; Pengfei Lin; Lemin Wei; Wenliang Ju (Science of The Total Environment, 2024)

Perfluorooctane sulfonate (PFOS) and benzo[a]pyrene (BaP) synergistically induce neurotoxicity in C6 rat glioma cells via the activation of neurotransmitter and Cyp1a1-mediated steroid hormone synthesis pathways - Yu-Shun Lu; Ju Chen; Xiao-Rong He; Shang-Lin Yang; Bing-Jie Ma; Jiang Yu; Jing Qiu; Yong-Zhong Qian; Yan-Yang Xu (Food and Chemical Toxicology, 2024)

Moderate strategy for efficient recovery of rare earth elements from scintillation crystal waste - Hao Chen; Yucheng Liu; Xiaowen Zhou; Wenyi Zhang; Peihai Ju; Xiaoyu Zhong; Jiuyang Lin; Yinhua Wan; Xuewei Li (Chemical Engineering Journal, 2024)

OsNAC15 regulates drought and salt tolerance in rice - Chuan-Wei Ao; Gan-ju Xiang; Yan-Fei Wu; Yue Wen; Zhong-Lin Zhu; Feng Sheng; Xuezhu Du (Physiology and Molecular Biology of Plants, 2024)

Mechanistic analyses reveal that Pueraria montana var. lobata (Willd.) is effective in inhibiting ovarian cancer progression - Chao Lin; Tong Su; Yong-ju Ye (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Synthesis of a novel double Z-scheme BiVO4/Cu2O/g-C3N4 sonocatalyst and research on sonocatalytic degradation of tetracycline - Yang-Cheng Liu; Ying-Di Ge; Hui-Li An; Wan-Ting Ju; Xin-Yi Zhou; Mei-Yi Xing; Yang Wang; Lin Zhang; Xin Wang; Liang Xu (Journal of Environmental Chemical Engineering, 2024)

Predicting concrete strength early age using a combination of machine learning and electromechanical impedance with nano-enhanced sensors - Huang Ju; Lin Xing; Alaa Hussein Ali; Islam Ezz El-Arab; Ali E.A. Elshekh; Mohamed Abbas; Nermeen Abdullah; Samia Elattar; Ahmed Hashmi; Elimam Ali; Hamid Assilzadeh (Environmental Research, 2024)

High-throughput generation of monodisperse double emulsions via controllable symmetric splitting in Y-shaped microchannels - Lin-Ling Fan; Wei Wang; Xiao-Jie Ju; Zhuang Liu; Rui Xie; Jianhong Xu; Guangsheng Luo; Da-Wei Pan; Liang-Yin Chu (Chemical Engineering Journal, 2024)

Two-Level regulation photocatalytic activity of Bi2WO6/COFs with ligand engineering and piezoelectric field for Highly-Efficient degradation of antibiotics - Yujun Ju; Hailong Lin; Chen Chen; Ruien Hou; Zhe Wang; Tinglong Hao; Min Xu; Yu Tang; Fengjuan Chen (Chemical Engineering Journal, 2024)

Dual-Salt aqueous electrolyte for enhancing Charge-Storage properties of VO2 polymorphic cathodes for Zn-Ion batteries - Jing-Hong Huang; Xu-Feng Luo; Tzu-Yu Kuo; Yu-Hua Lai; Purna Chandra Rath; Chun-Wei Huang; Ming-Hsien Lin; An-Yuan Hou; Ju Li; Yu-Sheng Su; Wen-Wei Wu; Jeng-Kuei Chang (Chemical Engineering Journal, 2024)

Population Pharmacokinetics of Casirivimab and Imdevimab in Pediatric and Adult Non-Infected Individuals, Pediatric and Adult Ambulatory or Hospitalized Patients or Household Contacts of Patients Infected with SARS-COV-2 - Kuan-Ju Lin; Kenneth C. Turner; Maria Rosario; Lutz O. Harnisch; John D. Davis; A. Thomas DiCioccio (Pharmaceutical Research, 2024)
Introduction Casirivimab (CAS) and imdevimab (IMD) are two fully human monoclonal antibodies that bind different epitopes on the receptor binding domain of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and block host receptor interactions. CAS + IMD and was developed for the treatment and prevention of SARS-CoV-2 infections. Methods A population pharmacokinetic (PopPK) analysis was conducted using pooled data from 7598 individuals from seven clinical studies to simultaneously fit concentration–time data of CAS and IMD and investigate selected covariates as sources of variability in PK parameters. The dataset comprised CAS + IMD-treated pediatric and adult non-infected individuals, ambulatory or hospitalized patients infected with SARS-CoV-2, or household contacts of patients infected with SARS-CoV-2. Results CAS and IMD concentration–time data were both appropriately described simultaneously by a two-compartment model with first-order absorption following subcutaneous dose administration and first-order elimination. Clearance estimates of CAS and IMD were 0.193 and 0.236 L/day, respectively. Central volume of distribution estimates were 3.92 and 3.82 L, respectively. Among the covariates identified as significant, body weight and serum albumin had the largest impact (20–34%, and ~ 7–31% change in exposures at extremes, respectively), while all other covariates resulted in small differences in exposures. Application of the PopPK model included simulations to support dose recommendations in pediatrics based on comparable exposures of CAS and IMD between different weight groups in pediatrics and adults following weight-based dosing regimens. Conclusions This analysis provided important insights to characterize CAS and IMD PK simultaneously in a diverse patient population and informed pediatric dose selection.

Analysis of Torsional Mechanical Behavior of Adjustable Air Cushion Sole Structures: Impact Simulation on Cutting Maneuvers - Md Samsul Arefin; Chien-Ju Lin; Hsiao-Feng Chieh; Kai-Nan An; Ying-Chun Huang; Fong-Chin Su (Journal of Medical and Biological Engineering, 2024)

The role of ferroptosis in DM-induced liver injury - Keping Wu; Jiasi Chen; Jiawen Lin; Enyi Zhu; Xiaochang Xu; Xiuhong Yan; Lang Ju; Mingcheng Huang; Yimin Zhang (BioMetals, 2024)

Assessing Normalized Difference Vegetation Index as a proxy of urban greenspace exposure - Yang Ju; Iryna Dronova; Qin Ma; Jian Lin; Mika R. Moran; Nelson Gouveia; Hong Hu; Haiwei Yin; Huiyan Shang (Urban Forestry & Urban Greening, 2024)

Micafungin protects mouse heart against doxorubicin-induced oxidative injury via suppressing MALT1-dependent k48-linked ubiquitination of Nrf2 - Li-Qun Lu; Ming-Rui Li; Lin-Lu Huang; Yan-Xi Che; Ya-Nan Qi; Xiu-Ju Luo; Jun Peng (Chemico-Biological Interactions, 2024)

ClinOleic Impairs ROS Production and Phagocytosis in M1 Macrophages Without Affecting M1 Differentiation - Yi-Sheng Tsai; Hsuan-Te Yeh; Ming-Shan Chen; Hui-Ju Chang; Wen-Chun Lin; Shew-Meei Sheu (Cell Biochemistry and Biophysics, 2024)

Assessments of 12 Commercial Species Stocks in a Subtropical Upwelling Ecosystem Using the CMSY and BSM Methods - Lin Chen; Peilong Ju; Zhenbin Lu; Cui Liang; Bin Chen; Jianguo Du; Ping Li (Fishes, 2024)
Twelve commercial species exploited in the eastern Guangdong and southern Fujian waters were assessed using the Catch-Maximum Sustainable Yield (CMSY) and Bayesian Schaefer Model (BSM) methods. The carrying capacity (k), intrinsic rate of population growth (r), maximum sustainable yield (MSY), and relative biomass (Bend/k and B/BMSY) were estimated. The current stock status was defined by B/BMSY and fishing mortality (F/FMSY). The results indicate that seven stocks were overfished or below safe biological limits (B/BMSY 1), two stocks were in a recovery phase (0.5 1, F/FMSY

Performances of full-scale biological nitrogen pre-treatment process for drinking water source: Seasonal variations and microbial community - Hai-Hsuan Cheng; Yee Han Hew; Yi-Ju Wu; Tin-Yin Chen; Yi Ting Chiu; Li Ying Chen; Tsair-Fuh Lin; Liang-Ming Whang (Chemosphere, 2024)

Exploring seasonal variations, assembly dynamics, and relationships of bacterial communities in different habitats of marine ranching - Cheng-Zhuang Chen; Ming-Hao Yin; Lin-Jing Niu; Jin-Xin Wang; Ling Liu; Yong-Jun Sun; Wen-Ming Ju; Ping Li; Zhi-Hua Li (Marine Pollution Bulletin, 2024)

Application of fluctuations in the sound field in inversion of internal solitary wave phase speed - Yingdong Zheng; Ju Lin; Xu Chen (Ocean Engineering, 2024)

Fluvoxamine Exerts Sigma-1R to Rescue Autophagy via Pom121-Mediated Nucleocytoplasmic Transport of TFEB - Chun-Yu Lin; Hsiang-En Wu; Eddie Feng-Ju Weng; Hsuan-Cheng Wu; Tsung-Ping Su; Shao-Ming Wang (Molecular Neurobiology, 2024)
Expansion of the GGGGCC-RNA repeat is a known cause of amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD), which currently have no cure. Recent studies have indicated the activation of Sigma-1 receptor plays an important role in providing neuroprotection, especially in ALS and Alzheimer’s disease. Nevertheless, the mechanisms underlying Sigma-1R activation and its effect on (G 4 C 2 )n-RNA-induced cell death remain unclear. In this study, we demonstrated that fluvoxamine is a Sigma-1R agonist that can increase chaperone activity and stabilize the protein expression of Pom121 in (G 4 C 2 ) 31 -RNA-expressing NSC34 cells, leading to increased colocalization at the nuclear envelope. Interestingly, fluvoxamine treatment increased Pom121 protein expression without affecting transcription. In C9orf72 -ALS, the nuclear translocation of TFEB autophagy factor decreased owing to nucleocytoplasmic transport defects. Our results showed that pretreatment of NSC34 cells with fluvoxamine promoted the shuttling of TFEB into the nucleus and elevated the expression of LC3-II compared to the overexpression of (G 4 C 2 ) 31 -RNA alone. Additionally, even when used alone, fluvoxamine increases Pom121 expression and TFEB translocation. To summarize, fluvoxamine may act as a promising repurposed medicine for patients with C9orf72 -ALS, as it stabilizes the nucleoporin Pom121 and promotes the translocation of TFEB in (G 4 C 2 ) 31 -RNA-expressing NSC34 cells.

A nationwide case-referent study on elevated risks of adenocarcinoma lung cancer by long-term PM2.5 exposure in Taiwan since 1997 - Wei-Chi Lin; Ruei-Hao Shie; Tzu-Hsuen Yuan; Chien-Hua Tseng; Chun-Ju Chiang; Wen-Chung Lee; Chang-Chuan Chan (Environmental Research, 2024)

GhGASA14 regulates the flowering time of upland cotton in response to GA3 - Ying Li; Wenmin Yuan; Jialuo Peng; Jisheng Ju; Pingjie Ling; Xuefeng Guo; Junning Yang; Qi Ma; Hai Lin; Jilian Li; Caixiang Wang; Junji Su (Plant Cell Reports, 2024)

Coupling hyperspectral imaging with machine learning algorithms for detecting polyethylene (PE) and polyamide (PA) in soils - Huan Chen; Taesung Shin; Bosoon Park; Kyoung Ro; Changyoon Jeong; Hwang–Ju Jeon; Pei-Lin Tan (Journal of Hazardous Materials, 2024)

Mechanisms and extended kinetic model of thermal desorption in organic-contaminated soil - Ximing Sun; Lin Zhao; Ju Hai; Xianwei Liang; Daying Chen; Jiashu Liu; Peisong Kang (Journal of Environmental Management, 2024)

Efficiencies of filtration sampling and extraction for recovery of viable Staphylococcus aureus bioaerosols - Ching-Wen Chang; Yen-Ni Lin; Sheng-Hsiu Huang; Yu-Ju Horng (Journal of Aerosol Science, 2024)

Paleoclimatic application of spectral parameters to the eolian red clay of the Jianzha Basin, northeastern margin of the Tibetan Plateau - Chaofeng Fu; Ju’e Tian; Xinwen Xu; Yougui Song; Jun Zuo; Feng Wang; Lin Chen; Pengfei Li; Xiaoke Qiang (Science China Earth Sciences, 2024)

RETRACTED ARTICLE: Micafungin exerts antitumor effect on breast cancer and osteosarcoma through preventing EMT in tumor cells in an USP7/AKT/GSK-3β pathway-dependent manner - Qian-Lin Wang; Li Wang; Qiong-Yu Li; Hui-Yin Li; Ling Lin; Dan Wei; Jin-Yun Xu; Xiu-Ju Luo (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Metabolomic profiling of maternal plasma identifies inverse associations of acetate and urea with anti-SARS-CoV-2 antibody titers following COVID-19 vaccination during pregnancy - An-Shine Chao; Chiao-Yun Lin; Meng-Han Chiang; Kuan-Ying Lu; Cheng-Kun Tsai; Kuan-Ju Chen; Chih-Wei Chien; Ting-Shu Wu; Yao-Lung Chang; Angel Chao; Gigin Lin; Chih-Yung Chiu (Journal of Molecular Medicine, 2024)

Selective dissolution of zinc and lead from duplex β-phase brasses in low and high conductivity water - Ming-Han Tsai; Shu-Ju Chao; Cai-lin Luo; Lap-Cuong Hua; Chi-Chang Hu; Biplab Kumar Mahata; Chihpin Huang (Chemosphere, 2024)

Analysis of the impact of indoor thermal comfort data characteristics on dataset quality - Chang Chang; Xiangli Li; Lin Duanmu; Bing Sun; Hengjin Ju (Energy and Buildings, 2024)

Crack Coalescence Mechanism and Crack Type Determination Model Based on the Analysis of Specimen Apparent Strain Field Data - Tao Dong; Ju Wang; Weiming Gong; Fei Wang; Hongguang Lin; Wengbo Zhu (Rock Mechanics and Rock Engineering, 2024)

The biocontrol potentials of rhizospheric bacterium Bacillus velezensis K0T24 against mulberry bacterial wilt disease - Wenlian Jiao; Ju Wen; Na Li; Ting Ou; Changyu Qiu; Yutong Ji; Kai Lin; Xiaojiao Liu; Jie Xie (Archives of Microbiology, 2024)

Occurrence and risk assessment of glycidyl and 3-monochloropropanediol esters in infant formulas marketed in Taiwan - Chen Liu; Shang-Ta Wang; Choon-Hui Tan; Zih-Ee Lin; Wei-Ju Lee (Food Additives & Contaminants: Part A, 2024)

Mapping multi-omics characteristics related to short-term PM2.5 trajectory and their impact on type 2 diabetes in middle-aged and elderly adults in Southern China - Jia-ting Wang; Wei Hu; Zhangzhi Xue; Xue Cai; Shi-yu Zhang; Fan-qin Li; Li-shan Lin; Hanzu Chen; Zelei Miao; Yue Xi; Tiannan Guo; Ju-Sheng Zheng; et al. (Journal of Hazardous Materials, 2024)

Spawning, larval morphological ontogeny and first feeding of yellow-striped cardinalfish Ostorhinchus cyanosoma (Bleeker, 1853) - Ang Lu; Xiang-Yu Li; Yi-Yang Lin; Yen-Ju Pan (Aquaculture, 2024)

A global synthesis of the patterns of genetic diversity in endangered and invasive plants - Zhi-Zhou He; Gisela C. Stotz; Xiang Liu; Jia-Jia Liu; Yu-Guo Wang; Ji Yang; Lin-Feng Li; Wen-Ju Zhang; Peng Nan; Zhi-Ping Song (Biological Conservation, 2024)

Evaluation of the dietary L-valine on fish growth and intestinal health after infection with Aeromonas veronii - Quanquan Cao; Ju Zhao; Lingjie He; Tianran Zhang; Lin Feng; Weidan Jiang; Pei Wu; Juan Zhao; Haifeng Liu; Jun Jiang (Aquaculture, 2024)

Assessment of sources and health risks of heavy metals in metropolitan household dust among preschool children: The LEAPP-HIT study - Chi-Sian Kao; Ying-Lin Wang; Chuen-Bin Jiang; Pei-Ju Tai; Yi-Hua Chen; Hsing-Jasmine Chao; Yu-Chun Lo; Zeng-Yei Hseu; Hsing-Cheng Hsi; Ling-Chu Chien (Journal of Environmental Management, 2024)

In-situ thermal conductive heating (TCH) for soil remediation: A review - Ximing Sun; Lin Zhao; Menglu Huang; Ju Hai; Xianwei Liang; Daying Chen; Jiashu Liu (Journal of Environmental Management, 2024)

An asymmetric electrode matching reversible kinetics of oxygen reaction for a rechargeable Zn-air battery - Shuxin Li; Han Zhang; Lin Wu; Hongwei Zhao; Lin Tao; Lixiang Li; Chengguo Sun; Dongying Ju; Baigang An (Chemical Engineering Journal, 2024)

Stronger latitudinal phylogenetic patterns in woody angiosperm assemblages with higher dispersal abilities in China - Lu Jin; Jia‐Jia Liu; Qiao‐Ming Li; Lu‐Xiang Lin; Xiao‐Na Shao; Tian‐Wen Xiao; Bu‐Hang Li; Xiang‐Cheng Mi; Hai‐Bao Ren; Yan Zhu; Xiu‐Juan Qiao; Ju‐Yu Lian; et al. (Journal of Biogeography, 2024)
Aim The equator‐to‐poles decline in the number of species, namely the latitudinal diversity gradient (LDG), is the most conspicuous pattern in biology, yet the underlying mechanisms of this pattern remain controversial. Species dispersal could have strong effects on large‐scale species distributions but has rarely been considered in understanding the LDG. Here we sought to examine how dispersal ability may influence the latitudinal phylogenetic patterns of woody angiosperm assemblages. Location China. Taxon Woody angiosperms. Methods Based on a highly supported mega‐phylogeny constructed from plastid genomes, we assessed the patterns of phylogenetic relatedness and dissimilarity of 1184 trees with three different seed dispersal modes (i.e. zoochory, anemochory and autochory) in 12 permanent forest dynamic plots covering tropical, subtropical and temperate zones in China. Results We found that, compared with zoochorous and anemochorous species, the less vagile autochorous trees exhibited a much weaker latitudinal pattern in phylogenetic relatedness and higher phylogenetic dissimilarity among plots. The phylogenetic dissimilarity pattern of autochorous trees was explained more by geographic distance than environmental factors, consistent with a dominant role for dispersal limitation. Main Conclusions Our study, for the first time, demonstrates that seed dispersal mode strongly influences the latitudinal phylogenetic patterns of woody angiosperm assemblages in China and highlights the importance of interaction between dispersal limitation and environmental filtering in determining the large‐scale distribution of forest biodiversity.

Vitamin D3 activates the innate immune response and xenophagy against Nocardia seriolae through the VD receptor in liver of largemouth bass (Micropterus salmoides) - Quanquan Cao; Ju Zhao; Mingyao Yan; Zhong Luo; Fu Luo; Lin Feng; Weidan Jiang; Pei Wu; Yan Wang; Debin Li; Haifeng Liu; Jun Jiang (Aquaculture, 2024)

Reciprocal transplant experiment reveals multiple factors influencing changes in coral microbial communities across climate zones - Ya-Fan Chan; Yu-Hsiang Chen; Sheng-Ping Yu; Hsing-Ju Chen; Yoko Nozawa; Sen-Lin Tang (Science of The Total Environment, 2024)

Ultra-efficient and selective adsorption of cationic dyes by Ti-doped SiO2 functionalized hydrophilic Fe3O4 nanoparticles with superior structural stability - Huishan Cai; Lin Zhang; Ju Wei; Yongrui Hou; Yuan Wei; Shunli Zhou; Zhenfu Jia; Xiaodong Su (Journal of Water Process Engineering, 2024)

Permafrost on the Tibetan Plateau is degrading: Historical and projected trends - Tongqing Shen; Peng Jiang; Qin Ju; Jiahui Zhao; Xuegao Chen; Hui Lin; Bin Yang; Changhai Tan; Ying Zhang; Xinting Fu; Zhongbo Yu (Journal of Hydrology, 2024)

Preliminary assessments of population exposure to glycidyl esters and 3-monochloropropane-1,2-diol esters from miscellaneous oil-containing packaged foods in Taiwan - Yu-Hsuan Chang; Kai-Wei Liao; Zih-Ee Lin; Wei-Ju Lee (Food Chemistry, 2024)

Modulating the microenvironment of catalytic interface with functional groups for efficient photocatalytic degradation of persistent organic pollutants - Yujun Ju; Ze Wang; Hailong Lin; Ruien Hou; Hua Li; Zhe Wang; Ruitong Zhi; Xiaoquan Lu; Yu Tang; Fengjuan Chen (Chemical Engineering Journal, 2024)

Ecological changes in subtidal macrobenthic communities of the Taean coast following the Hebei Spirit oil spill: A 10-year longitudinal study - Jae-Won Yoo; Chae-Lin Lee; Sungtae Kim; Eun-Ju Seong; Dong-Sik Ahn; Su-Young Jeong; Chang-Soo Kim; ByeongHo Kim; Byungkwan Jeong; Won-Ok Jeong (Marine Pollution Bulletin, 2023)

Analysis of enrichment, correlation, and leaching patterns of rare earth elements in coal fly ash assisted by statistical measures - Tongyao Ju; Yuan Meng; Siyu Han; Fanzhi Meng; Li Lin; Jinglin Li; Jianguo Jiang (Science of The Total Environment, 2023)

Experimental study on a concentrating solar photovoltaic/thermal system using different fluid spectral beam filters - Gang Wang; Xianglong Chen; Jianqing Lin; Chao Xu; Xing Ju (Journal of Cleaner Production, 2023)

Numerical modeling on nuclide transport around a nuclear waste repository under coupled thermo-hydro-mechanical condition - Jintong Zhang; Junyu Chen; Zhihong Zhao; Sicong Chen; Guihong Liu; Xingguang Zhao; Ju Wang; Tao Lin; Bing Liu (Computers and Geotechnics, 2023)

Frozen carbon is gradually thawing: Assessing interannual dynamics of thawed soil organic carbon stocks in the Tibetan Plateau permafrost area from 1901−2020 - Tongqing Shen; Peng Jiang; Qin Ju; Xuegao Chen; Hui Lin; Jiahui Zhao; Fan Zhang; Zhongbo Yu (Agricultural and Forest Meteorology, 2023)

Miticidal activity of Photorhabdus luminescens for controlling two spider mites, Tetranychus urticae and Tetranychus kanzawai, in Carica papaya - Tzay-Tien Hsieh; Ju-Chun Chang; Chienyan Hsieh; Jui-Tang Tseng; Show-Jow Lin; Cheng-Ju Yang; Feng-Chia Hsieh; Yu-Shin Nai (BioControl, 2023)

A resilience assessment framework for existing underground structures under adjacent construction disturbance - Kaihang Han; Dongmei Zhang; Xiangsheng Chen; Dong Su; Jiann-Wen Woody Ju; Xing-Tao Lin; Hongzhi Cui (Tunnelling and Underground Space Technology, 2023)

The complex role of air pollution on the association between greenness and respiratory mortality: Insight from a large cohort, 2009–2020 - Wenjing Wu; Zhicheng Du; Ying Wang; Yuqin Zhang; Shirui Chen; Xu Ju; Gonghua Wu; Zhiqaing Li; Jie Sun; Jie Jiang; Weihua Hu; Ziqiang Lin; et al. (Science of The Total Environment, 2023)

Spatial-temporal dynamics of meteorological and soil moisture drought on the Tibetan Plateau: Trend, response, and propagation process - Hui Lin; Zhongbo Yu; Xuegao Chen; Huanghe Gu; Qin Ju; Tongqing Shen (Journal of Hydrology, 2023)

Hydroxyl-groups engineering of triazole-based polymers for efficient photocatalytic hydrogen peroxide production - Feng Lin; Zhaoyang Ju; Yao Li; Jia Liu; Liyong Ding; Haijie Ben; Yulin Wang; Yuechao Wu; Ying Lei; Huiming Zeng; Shaohong Zang; Jun Chen; et al. (Journal of Cleaner Production, 2023)

Experimental studies on improving progressive collapse resistance of RC beam–column assemblies using kinked steel plates - Xing-Ju Yang; Feng Lin; Xiang-Lin Gu (Engineering Structures, 2023)

Preparation, characterization, and evaluation of the antitumor effect of kaempferol nanosuspensions - Wen He; Junfeng Zhang; Jiale Ju; Yinghua Wu; Yuxi Zhang; Lin Zhan; Chenchen Li; Yanli Wang (Drug Delivery and Translational Research, 2023)

Accumulation degree and risk assessment of metals in street dust from a developing city in Central Taiwan - Tser-Sheng Lin; Jun-Wei Wu; Thi-Dieu-Hien Vo; Van-Truc Nguyen; Yun-Ru Ju (Chemosphere, 2023)

The growth inhibitory effects and non-targeted metabolomic profiling of Microcystis aeruginosa treated by Scenedesmus sp - Xiao-lin Zhang; Qian-qian Zhu; Chuan-yue Chen; Bing Xie; Bin-guo Tang; Mei-hua Fan; Qun-ju Hu; Zhi Liao; Xiao-jun Yan (Chemosphere, 2023)

Analysis of green certification standards related to recycled materials involving textiles based on life cycle thinking - Hsin-Ju Lin; Hwong-wen Ma (Sustainable Production and Consumption, 2023)

Dendrobium officinale aqueous extract regulates bile acid synthesis to improve acute alcoholic liver injury in mice - Ju Ye; Di Wu; Xingdong Wu; Lin Qin; Mengting Yang; Yan-liu Lu; Dao-peng Tan; Yu-qi He (Food Bioscience, 2023)

Study on the effectiveness of ionic liquid-based biphasic amine solvent in removing H2S, NH3 and CO2 from biogas and its influential characteristics - Fanzhi Meng; Tongyao Ju; Siyu Han; Li Lin; Jinglin Li; Kailun Chen; Jianguo Jiang (Chemical Engineering Journal, 2023)

Microbiome assembly mechanism and functional potential in enhanced biological phosphorus removal system enriched with Tetrasphaera-related polyphosphate accumulating organisms - Hui Wang; Limin Lin; Lu Zhang; Ping Han; Feng Ju (Environmental Research, 2023)

Sequential deacetylation/self-gelling chitin hydrogels and scaffolds functionalized with fucoidan for enhanced BMP-2 loading and sustained release - Hsien-Tsung Lu; Chi Lin; Yi-Ju Wang; Fang-Yu Hsu; Ju-Ting Hsu; Min-Lang Tsai; Fwu-Long Mi (Carbohydrate Polymers, 2023)

Harnessing split fluorescent proteins in modular protein logic for advanced whole-cell detection - Ping-Heng Lin; Ssu-Tzu Tsai; Yu-Chia Chang; Yi-Ju Chou; Yi-Chun Yeh (Analytica Chimica Acta, 2023)

Evolutionary roles of polyploidization‐derived structural variations in the phenotypic diversification of Panax species - Yu‐Xin Zhang; Xin‐Feng Wang; Yu‐Qian Niu; Yu‐Guo Wang; Wen‐Ju Zhang; Zhi‐Ping Song; Ji Yang; Lin‐Feng Li (Molecular Ecology, 2023)
Genomic structural variations (SVs) are widespread in plant and animal genomes and play important roles in phenotypic novelty and species adaptation. Frequent whole genome duplications followed by (re)diploidizations have resulted in high diversity of genome architecture among extant species. In this study, we identified abundant genomic SVs in the Panax genus that are hypothesized to have occurred through during the repeated polyploidizations/(re)diploidizations. Our genome‐wide comparisons demonstrated that although these polyploidization‐derived SVs have evolved at distinct evolutionary stages, a large number of SV‐intersecting genes showed enrichment in functionally important pathways related to secondary metabolites, photosynthesis and basic cellular activities. In line with these observations, our metabolic analyses of these Panax species revealed high diversity of primary and secondary metabolites both at the tissue and interspecific levels. In particular, genomic SVs identified at ginsenoside biosynthesis genes, including copy number variation and large fragment deletion, appear to have played important roles in the evolution and diversification of ginsenosides. A further herbivore deterrence experiment demonstrated that, as major triterpenoidal saponins found exclusively in Panax , ginsenosides provide protection against insect herbivores. Our study provides new insights on how polyploidization‐derived SVs have contributed to phenotypic novelty and plant adaptation.

Effects of winemaking techniques on the phenolics, organic acids, and volatile compounds of Muscat wines - Yan-lun Ju; Xue-lei Xu; Yi-ke Yu; Meng Liu; Wan-ni Wang; Jin-ren Wu; Bo-chen Liu; Yang Zhang; Yu-lin Fang (Food Bioscience, 2023)

A rapid and effective method for obtaining ardicrenin from Ardisia crenata Sims var. bicolor plants - Zhen Lin; Xiuling Yang; Lin Li; Chunyan Ma; Lingjuan Kong; Huancheng Li; Shican Xiong; Haiyan Zhong; Shangrao Pu; Fang Liang; Ju Hu (Brazilian Journal of Botany, 2023)

A green and multi-win strategy for coal fly ash disposal by CO2 fixation and mesoporous silica synthesis - Tongyao Ju; Yuan Meng; Siyu Han; Fanzhi Meng; Li Lin; Jinglin Li; Yufeng Du; Mengzhu Song; Tian Lan; Jianguo Jiang (Science of The Total Environment, 2023)

Comprehensive study of recycling municipal solid waste incineration fly ash in lightweight aggregate with bloating agent: Effects of water washing and bloating mechanism - Siyu Han; Tongyao Ju; Fanzhi Meng; Li Lin; Jinglin Li; Kailun Chen; Jianguo Jiang (Science of The Total Environment, 2023)

Potential causal links between long-term ambient particulate matter exposure and cerebrovascular mortality: Insights from a large cohort in southern China - Shirui Chen; Xiao Lin; Zhicheng Du; Yuqin Zhang; Lingling Zheng; Xu Ju; Tong Guo; Xinran Wang; Lichang Chen; Jie Jiang; Weihua Hu; Wangjian Zhang; et al. (Environmental Pollution, 2023)

Understanding occupancy patterns of university libraries in the post-pandemic era - Yi Ju; Zhe Wang; Xinyuan Ju; Bin Cao; Chen Chen; Borong Lin (Energy and Buildings, 2023)

Phylogenetic divergence associated with climate oscillations and topology illustrates the dispersal history of Formosan sambar deer (Rusa unicolor swinhoii) in Taiwan - Kuan-Yi Li; Chen Hsiao; Shih-Ching Yen; Chien-Yi Hung; You-Zhu Lin; Sheng-Wun Jheng; Pei-Ju Yu; Mei-Hsiu Hwang; Guo-Jing Weng; Ku-Lin Chen; Shu-Fen Lin; Shih-Wei Chang; et al. (Mammal Research, 2023)
The island of Taiwan represents an ideal context for studying the effects of climatic oscillations and topographic variation on large herbivores due to its varied tropical to sub-tropical climate zones at different elevational ranges. We explored the phylogenetics of Formosan sambar deer ( Rusa unicolor swinhoii ) using the control region of the mitochondrial genome. We detected 18 haplotypes among 454 sequences across the island and grouped them into six regions based on SAMOVA, with 68.78% variance among regions. A Bayesian phylogenetic dendrogram revealed two spatially segregated genetic clades. Neutrality tests and Bayesian skyline plots uncovered different demographic expansion histories for the two clades. We further tested divergence times and chronology to propose potential phylogenetic scenarios, which were examined using approximate Bayesian computation. Finally, we present a credible hypothesis for a glacial refugium in the northern part of the Central Mountain Range. Subsequent secondary contact between the two clades during interglacial periods has led to the extant genetic structure of Formosan sambar deer.

Exposure to acrylamide induces zygotic genome activation defects of mouse embryos - Si-Le Wu; Jia-Qian Ju; Yi-Ming Ji; Hao-Lin Zhang; Yuan-Jing Zou; Shao-Chen Sun (Food and Chemical Toxicology, 2023)

High electric field-induced ferroelectric loss of polymer/paraelectric barium titanate particle nanocomposites - Elshad Allahyarov; Qiong Li; Tianxiong Ju; Yeu-Wei Harn; Hang Luo; Dou Zhang; Zhiqun Lin; Lei Zhu (Chemical Engineering Journal, 2023)

pH and non-enzymatic glucose response at ultra-low concentration using submicrochannel heterogeneous membrane - Yuan-Ju Tang; Kai Cheng; Lin-Fang Tan; Xiao-Ting Xie; Bin Zhang; Wen-Ming Su; Yuan-Di Zhao; Qiu-Ran Xu (Chemical Engineering Journal, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

FexO4-enhanced degradation of bisphenol A in visible light/peroxydisulfate system: production of singlet state oxygen - Zhimin Xu; Shaohua Ju; Peng Gao; Junjian Lin; Yifan Niu; Fei Meng; Shunling Li; Fangfang Li; Jiahao Du; Li Xu; Hongbo Peng; Bo Pan (Environmental Science and Pollution Research, 2023)

Time to reconsider the enigmatic tail of eastern Paleo-Tethys: New insights from Borneo - Xiao Ran Zhang; Sun-Lin Chung; Azman A. Ghani; Rezal Rahmat; Yi-Ju Hsin; Hao-Yang Lee; Ping-Ping Liu; Jinyu Xi (Lithos, 2023)

Lactobacillus plantarum isolated from kefir enhances immune responses and survival of white shrimp (Penaeus vannamei) challenged with Vibrio alginolyticus - Kuo-Chun Tseng; Huai-Ting Huang; Shu-Ning Huang; Fang-Yi Yang; Wen-Hsiung Li; Fan-Hua Nan; Yu-Ju Lin (Fish & Shellfish Immunology, 2023)

Novel monoethanolamine absorption using ionic liquids as phase splitter for CO2 capture in biogas upgrading: High CH4 purity and low energy consumption - Fanzhi Meng; Tongyao Ju; Siyu Han; Li Lin; Jinglin Li; Kailun Chen; Jianguo Jiang (Chemical Engineering Journal, 2023)

Deciphering basic and key traits of antibiotic resistome in influent and effluent of hospital wastewater treatment systems - Lin Zhu; Ling Yuan; Xin-Yi Shuai; Ze-Jun Lin; Yu-Jie Sun; Zhen-Chao Zhou; Ling-Xuan Meng; Feng Ju; Hong Chen (Water Research, 2023)

Preparation of alumina/silica/exfoliated graphite nanoplatelets composite aerogels and its application as supporting material for erythritol based form-stable phase change materials - Yu-Hao Ning; Ye Tan; Chuan-Huang Lin; Qi Li; Lin-Ping Yu; Zhong Cao; Li-Xian Sun; Chuan-Chang Li; Ju-Lan Zeng (Chemical Engineering Journal, 2023)

Trade-offs between fertilizer-N availability and Cd pollution potential under crop straw incorporation by 15 N stable isotopes in rice - Anqi Shan; Lukuan Huang; Dan Chen; Qiang Lin; Rongjie Liu; Mei Wang; Kyong Ju Kang; Minghui Pan; Gang Wang; Zhenli He; Xiaoe Yang (Environmental Science and Pollution Research, 2023)

Facile synthesis of triazine-based microporous organic network for high-efficient adsorption of flumequine and nadifloxacin: A comprehensive study on adsorption mechanisms and practical application potentials - Zhe Zhao; Shumin Lin; Zhendong Yu; Ming Su; Bolong Liang; Shu-Xuan Liang; Xue-Hai Ju (Chemosphere, 2023)

PM2.5 induces the abnormal lipid metabolism and leads to atherosclerosis via Notch signaling pathway in rats - Tianyang Zhao; Xu Li; Honghao Qian; Xiaohan Miao; Ying Zhu; Jia Wang; Ju Hui; Liting Zhou; Lin Ye (Toxicology, 2023)

Changes in permafrost spatial distribution and active layer thickness from 1980 to 2020 on the Tibet Plateau - Tongqing Shen; Peng Jiang; Qin Ju; Zhongbo Yu; Xuegao Chen; Hui Lin; Yueguan Zhang (Science of The Total Environment, 2023)

In situ derived sulfated/sulfonated carbon nanogels with multi-protective effects against influenza a virus - Hung-Yun Lin; Ka-Long Luo; Ju-Yi Mao; Chin-Jung Lin; Chen-Yow Wang; Lauren Panny; Shiow-Yi Chen; Shih-Chao Lin; Chih-Ching Huang; Scott G. Harroun; Robert Y.L. Wang; Chang-Jer Wu (Chemical Engineering Journal, 2023)

Correction to: Microplastic pollution and its impact on marine microbes in Zhanjiang, China - Qing-Lang Song; Fang-Hong Nie; Di-Hua Zhu; Yun-Li Wei; Min Zhang; Yao Hu; Meng-Meng Chen; Dan-Ju Kang; Zhi-Bao Chen; Hong-Ying Lin; Jin-Jun Chen (Journal of Coastal Conservation, 2023)

SERS detection of thiram using polyacrylamide hydrogel-enclosed gold nanoparticle aggregates - Kaiqiang Wang; Zilin Yue; Xiu Fang; Hong Lin; Lei Wang; Limin Cao; Jianxin Sui; Lei Ju (Science of The Total Environment, 2023)

Novel multifunctional natural selenium supplement development, in vitro and in vivo analysis, and risk-benefit assessment: Selenium-enriched chicory as a case study - Yaolei Li; Shanshan Ju; Jinjian Huang; Hao Wu; Zhijian Lin; Yu Wang; Hongyu Jin; Shuangcheng Ma; Bing Zhang (Journal of Cleaner Production, 2023)

Characteristics, application and modeling of solid amine adsorbents for CO2 capture: A review - Li Lin; Yuan Meng; Tongyao Ju; Siyu Han; Fanzhi Meng; Jinglin Li; Yufeng Du; Mengzhu Song; Tian Lan; Jianguo Jiang (Journal of Environmental Management, 2023)

Environmental concentrations of benzophenone-3 disturbed lipid metabolism in the liver of clown anemonefish (Amphiprion ocellaris) - Yan-Kun Zhang; Huai-Yang Ke; Yong-Qiang Qin; Han-Ye Ju; Yu-Mei Chen; Fang Lin; Ji-Liang Zhang; Xiao-Ping Diao (Environmental Pollution, 2023)

Identification of serum metabolic signatures of environmental-leveled phthalate in the Taiwanese child population using NMR-based metabolomics - Sheng-Han Lee; Zhi-Yi Du; Wei-Chen Tseng; Wan-Yu Lin; Mei-Huei Chen; Ching-Chun Lin; Hao-Jan Liang; Hui-Ju Wen; Yue-Leon Guo; Pau-Chung Chen; Ching-Yu Lin (Environmental Pollution, 2023)

Synthesis of N-doped sludge biochar using the hydrothermal route-enabled carbonization method for the efficient degradation of organic pollutants by peroxymonosulfate activation - Battuya Byambaa; Eun-Ju Kim; Mingizem Gashaw Seid; Byung-Min An; Jinsoo Cho; Shine Lin Aung; Kyung Guen Song (Chemical Engineering Journal, 2023)

Generation of reactive oxygen species through dissolved oxygen activation on defected porous carbon for efficient degradation of antibiotics - Jiaming Liu; Zhangwei Yao; Genping Qiu; Yinhua Wan; Weijie Song; Huifeng Zeng; Feifei Yang; Da Zhao; Wenjing Yuan; Peihai Ju; Ruixi Lin; Hengcheng Zhou; et al. (Chemical Engineering Journal, 2023)

Lanthanum-modified polydopamine loaded Acinetobacter lwoffii DNS32 for phosphate and atrazine removal: Insights into co-adsorption and biodegradation mechanisms - Siyue Han; Yue Tao; Yunhe Cui; Jiaming Xu; Hanxun Ju; Linlin Fan; Lin Zhang; Ying Zhang (Bioresource Technology, 2023)

High level of somatic mutations detected in a diploid banana wild relative Musa basjoo - Yilun Ji; Xiaonan Chen; Shengqiu Lin; Milton Brian Traw; Dacheng Tian; Sihai Yang; Long Wang; Ju Huang (Molecular Genetics and Genomics, 2023)

Insm1 promotes differentiation of retinal progenitor cells toward photoreceptor cells in the developing retina through up-regulation of SHH - Pengyi Zhou; Youmei Xu; Lin Yang; Pan Meng; Ju Guo; Zhenhui Liu; Bo Jin; Kunpeng Xie; Haiyan Zhu; Liping Du; Xuemin Jin (Journal of Molecular Histology, 2022)

Microplastic pollution and its impact on marine microbes in Zhanjiang, China - Qing-Lang Song; Fang-Hong Nie; Di-Hua Zhu; Yun-Li Wei; Min Zhang; Yao Hu; Meng-Meng Chen; Dan-Ju Kang; Zhi-Bao Chen; Hong-Ying Lin; Jin-Jun Chen (Journal of Coastal Conservation, 2022)

Effects of Ran-GTP/importin β inhibition on the meiotic division of porcine oocytes - Yijing He; Jia Li; Lei Peng; Qiao Li; Yajie Chu; Qixin Lin; Jianjun Dai; Rong Rui; Shiqiang Ju (Histochemistry and Cell Biology, 2022)

Countrywide inter‐epidemic region migration pattern suggests the role of southwestern population in wheat stripe rust epidemics in China - Muhammad Awais; Sajid Ali; Meng Ju; Wei Liu; Gensheng Zhang; Zedong Zhang; Zejian Li; Xinyao Ma; Lin Wang; Zhimin Du; Xiaxia Tian; Qingdong Zeng; et al. (Environmental Microbiology, 2022)
Understanding countrywide pathogen population structure and inter‐epidemic region spread is crucial for deciphering crop potential losses. Wheat stripe rust caused by Puccinia striiformis f. sp. tritici is a destructive disease that affects worldwide wheat production, widespread in China, representing largest epidemic region globally. This study aimed to understand the population structure and migration route of P . striiformis f. sp. tritici across China based on sampling from 15 provinces representing six epidemic zones, viz., over‐summering, over‐wintering, eastern, Yun‐Gui, Xinjiang and Tibet epidemic regions. High genotypic diversity was recorded in over‐summering, Tibet and over‐wintering epidemic regions. Epidemic regions partly explain population subdivision with variable divergence ( F ST = 0.005–0.344). Xinjiang and Tibet epidemic regions were independent epidemic zones with least sharing of genotypes. Among other epidemic zones, i.e. over‐summering, over‐wintering, eastern and Yun‐Gui epidemic zones, re‐sampling MLGs, clustering‐based structure, DAPC analyses, relative migration and low divergence ( F ST from 0.006 to 0.073) revealed frequent geneflow. Yun‐Gui epidemic regions, with a potential for both over‐summering and over‐wintering, could play an important role in causing epidemics in main wheat‐cultivating areas of China. High diversity, recombination signatures and inter‐epidemic region migration patterns need to be considered in host‐resistant cultivar development in China and neighbouring countries, considering risk of long‐distance migration capacity of pathogen.

Correction to: Exosome-Derived lncRNA NEAT1 Exacerbates Sepsis-Associated Encephalopathy by Promoting Ferroptosis Through Regulating miR-9-5p/ TFRC and GOT1 Axis - Xue-biao Wei; Wen-qiang Jiang; Ju-hao Zeng; Lin-qiang Huang; Hong-guang Ding; Yuan-wen Jing; Yong-li Han; Yi-chen Li; Sheng-long Chen (Molecular Neurobiology, 2022)

Fine particulate matter measured by satellites predicts the risk of age-related macular degeneration in a longitudinal cohort study - Chung-Ling Liang; Chi-Min Wang; Chau-Ren Jung; Ya-Chu Chang; Chun-Ju Lin; Yu-Ting Lin; Bing-Fang Hwang (Environmental Science and Pollution Research, 2022)

High Levels of 25-OH-Vitamin D and Copper in Pregnant Women with Abnormal Glucose Challenge Test - Chien-Hua Chiang; Wan-Ju Kung; Chien-Hung Lee; Yeong-Hwa Zen; Cheng-Fa Lee; Hui-Ru Yang; Ching-Chiang Lin; Yeou-Lih Huang (Biological Trace Element Research, 2022)

Elevated α-synuclein and NfL levels in tear fluids and decreased retinal microvascular densities in patients with Parkinson’s disease - Chao-Wen Lin; Tzu-Ting Lai; Szu-Ju Chen; Chin-Hsien Lin (GeroScience, 2022)

Effects of Environmental and Spatial Variables on Bacteria in Zhanjiang Mangrove Sediments - Di-Hua Zhu; Qing-Lang Song; Fang-Hong Nie; Wan Wei; Meng-Meng Chen; Min Zhang; Hong-Ying Lin; Dan-Ju Kang; Zhi-Bao Chen; Anthony G. Hay; Jin-Jun Chen (Current Microbiology, 2022)

Temperature Affects Antagonism Among Coral-Associated Bacteria - Anjie Guo; Jie Li; Lin Wang; Huimin Ju; Qiqi Li; Lijuan Ren; Si Zhang (Frontiers in Marine Science, 2022)
Reef-building corals are invertebrate animals that associate with diverse microorganisms, including Symbiodiniaceae, bacteria, fungi, and archaea. This symbiotic consortium, called the holobiont, is a dynamic system and rapidly responds to environmental temperatures. At present, the effects of temperature on bacteria-bacteria interactions in the coral-associated bacterial community are not clear. Antagonism is considered one of the potential structuring forces in coral microbial communities. Here, we examined the antagonistic interactions among 32 coral-associated bacteria and the physiological and biochemical characteristics of these isolates at different temperatures. The results showed that the antagonism breadth (i.e. the total number of antagonistic interactions) increased but antagonism intensity (i.e. the size of the inhibition zone) decreased at 32°C. The antagonistic interaction network was nested and sender-determined both at 25°C and 32°C, suggesting that the competition networks of coral-associated bacteria were more influenced by the antagonist strains than sensitive strains. Furthermore, we found that the elevated temperature increased the complexity of the antagonistic network. By evaluating the correlations between antagonism and the phylogenetic and phenotypic distances, we demonstrated that the antagonism probability correlated with the phylogenetic distance rather than phenotypic distance. Moreover, the antagonist strains have a wider metabolic niche space, i.e., grew on more carbon sources, than the antagonized strains at 25°C, while there was no difference at 32°C, suggesting the trade-off between antagonism and resource exploitation shifted in the antagonistic interactions under the higher temperature. These findings will be helpful for understanding the bacterial interactions in coral holobionts and the assembly of bacterial community in altered environments, especially under heat stress.

Exosome-Derived lncRNA NEAT1 Exacerbates Sepsis-Associated Encephalopathy by Promoting Ferroptosis Through Regulating miR-9-5p/TFRC and GOT1 Axis - Xue-biao Wei; Wen-qiang Jiang; Ju-hao Zeng; Lin-qiang Huang; Hong-guang Ding; Yuan-wen Jing; Yong-li Han; Yi-chen Li; Sheng-long Chen (Molecular Neurobiology, 2022)
Sepsis can cause sepsis-associated encephalopathy (SAE), but whether SAE was induced or exacerbated by ferroptosis remains unknown. In this study, the rat sepsis model was constructed using the cecal ligation and puncture method. The blood–brain barrier (BBB) permeability was measured by Evans blue dye (EBD) in vivo. The levels of ROS, Fe ion, MDA, GSH, and GPX4 were assessed by enzyme-linked immunosorbent assay (ELISA). The exosomes isolated from serum were cultured with bEnd.3 cells for the in vitro analysis. Moreover, bEnd.3 cells cultured with 100 μM FeCl3 (iron-rich) were to simulate ferroptosis stress. The cell viability was evaluated by Cell Counting Kit-8 (CCK-8) assay. A dual-luciferase reporter gene assay was performed to confirm the relationship between miR-9-5p with NEAT1, TFRC , and GOT1 . In vivo, it is found that BBB permeability was damaged in model rats. Level of ROS, Fe ion, and MDA was increased, and level of GSH and GPX4 was decreased, which means ferroptosis was induced by sepsis. Exosome-packaged NEAT1 in serum was significantly upregulated in model rats. In vitro, it is found that NEAT1 functions as a ceRNA for miR-9-5p to facilitate TFRC and GOT1 expression. Overexpression of NEAT1 enhanced ferroptosis stress in bEnd.3 cells. Increased miR-9-5p alleviated sepsis-induced ferroptosis by suppressing the expression of TFRC and GOT1 both in vivo and in vitro. In conclusion, these findings suggest that sepsis induced high expression of serous exosome-derived NEAT1, and it might exacerbate SAE by promoting ferroptosis through regulating miR-9-5p/ TFRC and GOT1 axis.

Prevalence, complete genome, and metabolic potentials of a phylogenetically novel cyanobacterial symbiont in the coral‐killing sponge, Terpios hoshinota - Yu‐Hsiang Chen; Hsing‐Ju Chen; Cheng‐Yu Yang; Jia‐Ho Shiu; Daphne Z. Hoh; Pei‐Wen Chiang; Wenhua Savanna Chow; Chaolun Allen Chen; Tin‐Han Shih; Szu‐Hsien Lin; Chi‐Ming Yang; James Davis Reimer; et al. (Environmental Microbiology, 2022)
Summary Terpios hoshinota is an aggressive, space‐competing sponge that kills various stony corals. Outbreaks of this species have led to intense damage to coral reefs in many locations. Here, the first large‐scale 16S rRNA gene survey across three oceans revealed that bacteria related to the taxa Prochloron , Endozoicomonas , SAR116, Ruegeria , and unclassified Proteobacteria were prevalent in T . hoshinota . A Prochloron ‐related bacterium was the most dominant and prevalent cyanobacterium in T . hoshinota . The complete genome of this uncultivated cyanobacterium and pigment analysis demonstrated that it has phycobiliproteins and lacks chlorophyll b , which is inconsistent with the definition of Prochloron . Furthermore, the cyanobacterium was phylogenetically distinct from Prochloron , strongly suggesting that it should be a sister taxon to Prochloron . Therefore, we proposed this symbiotic cyanobacterium as a novel species under the new genus Candidatus Paraprochloron terpiosi. Comparative genomic analyses revealed that ‘Paraprochloron’ and Prochloron exhibit distinct genomic features and DNA replication machinery. We also characterized the metabolic potentials of ‘Paraprochloron terpiosi’ in carbon and nitrogen cycling and propose a model for interactions between it and T. hoshinota . This study builds a foundation for the study of the T . hoshinota microbiome and paves the way for better understanding of ecosystems involving this coral‐killing sponge.

Distinct durability of IgM/IgG antibody responses in COVID-19 patients with differing severity - Junyan Han; Ning Zhang; Danying Chen; Yuhuan Gong; Guoli Li; Yaxian Kong; Lin Pu; Chen Chen; Jingyuan Liu; Qi Wang; Ju Zhang; Xuesen Zhao; et al. (Science China Life Sciences, 2022)

An innovative targeted therapy for fluoroscopy-induced chronic radiation dermatitis - Kai-Che Wei; Shih-Fan Lai; Wei-Lun Huang; Kuo-Chung Yang; Ping-Chin Lai; Wan-Ju Wei; Tsung-Hsien Chang; Yun-Chen Huang; Ya-Chuan Tsai; Shin-Chih Lin; Sun-Jang Lin; Shih-Chieh Lin (Journal of Molecular Medicine, 2022)
Fluoroscopy-induced chronic radiation dermatitis (FICRD) is a complication of fluoroscopy-guided intervention. Unlike acute radiation dermatitis, FICRD is different as delayed onset and usually appears without preexisting acute dermatitis. Unfortunately, the chronic and progressive pathology of FICRD makes it difficult to treat, and some patients need to receive wide excision and reconstruction surgery. Due to lack of standard treatment, investigating underlying mechanism is needed in order to develop an effective therapy. Herein, the Hippo pathway is specifically identified using an RNA-seq analysis in mild damaged skin specimens of patients with FICRD. Furthermore, specific increase of the Yes-associated protein (YAP1), an effector of the Hippo pathway, in skin region with mild damage plays a protective role for keratinocytes via positively regulating the numerous downstream genes involved in different biological processes. Interestingly, irradiated-keratinocytes inhibit activation of fibroblasts under TGF-β1 treatment via remote control by an exosome containing YAP1. More importantly, targeting one of YAP1 downstream genes, nuclear receptor subfamily 3 group C member 1 (NR3C1), which encodes glucocorticoid receptor, has revealed its therapeutic potential to treat FICRD by inhibiting fibroblasts activation in vitro and preventing formation of radiation ulcers in a mouse model and in patients with FICRD. Taken together, this translational research demonstrates the critical role of YAP1 in FICRD and identification of a feasible, effective therapy for patients with FICRD. Key messages • YAP1 overexpression in skin specimens of radiation dermatitis from FICRD patient. • Radiation-induced YAP1 expression plays protective roles by promoting DNA damage repair and inhibiting fibrosis via remote control of exosomal YAP1. • YAP1 positively regulates NR3C1 which encodes glucocorticoid receptor expression. • Targeting glucocorticoid receptor by prednisolone has therapeutic potential for FICRD patient.

The effects of immersive garden experience on the health care to elderly residents with mild-to-moderate cognitive impairment living in nursing homes after the COVID-19 pandemic - Chung-Heng Hsieh; Cheng-Min Chen; Ju-Yuan Yang; Yen-Ju Lin; Man-Li Liao; Ke-Hsin Chueh (Landscape and Ecological Engineering, 2022)

A comparison of atmospheric geochemistry through lichens from volcanic and non-volcanic areas, north Taiwan - Le-Qi Lin; Hsueh-Yu Lu; Ju-Lien Pi; Tai-Sheng Liou; Wen-Fu Chen; Pei-Shan Hsieh (Journal of Earth System Science, 2021)

Applicability evaluation and improvement of different snow evaporation calculation methods in the Great Xing’an mountains - Youwei Lin; Tijiu Cai; Cunyong Ju; Xueqing Cui (Earth Science Informatics, 2021)

Acquired dysgraphia in a girl with subcortical band heterotopia - Shan-Ju Lin; Wei-Sheng Lin (Acta Neurologica Belgica, 2021)

Investigation of biofilm formation in methicillin-resistant Staphylococcus aureus associated with bacteraemia in a tertiary hospital - Wen Kiong Niek; Cindy Shuan Ju Teh; Nuryana Idris; Kwai Lin Thong; Soo Tein Ngoi; Sasheela Sri La Sri Ponnampalavanar (Folia Microbiologica, 2021)

Resveratrol Mitigates Cerebral Ischemic Injury by Altering Levels of Trace Elements, Toxic Metal, Lipid Peroxidation, and Antioxidant Activity - Ju-Hai Ro; Chien-Chi Liu; Ming-Cheng Lin (Biological Trace Element Research, 2021)

Microorganism and Physiochemical Characteristic of High-salt (Suan Yu), a Traditional Chinese Fermented Fish - Chengxing Lin; Furong Zhang; Qin Yang; Ju Meng; Laping He; Li Deng; Chun Ye; Xuefeng Zeng (Journal of Aquatic Food Product Technology, 2021)

Contamination, source attribution, and potential health risks of heavy metals in street dust of a metropolitan area in Southern Vietnam - Nguyen Duy Dat; Van-Truc Nguyen; Thi-Dieu-Hien Vo; Xuan-Thanh Bui; Manh-Ha Bui; Ly Sy Phu Nguyen; Xuan-Cuong Nguyen; Anh Thi-Kim Tran; Thi-Tinh-Au Nguyen; Yun-Ru Ju; Thi-Minh-Trang Huynh; Duy-Hieu Nguyen; et al. (Environmental Science and Pollution Research, 2021)

Cortisol and glucocorticoid receptor 2 regulate acid secretion in medaka (Oryzias latipes) larvae - Chia-Hao Lin; Huei-Jyun Hu; Hsin-Ju Chuang; Yi-Ling Tsou; Pung-Pung Hwang (Journal of Comparative Physiology B, 2021)

Patient Confidential Information Transmission Using the Integration of PSO-Based Biomedical Signal Steganography and Threshold-Based Compression - Shih-Ying Chen; Shan-Ju Lin; Ming-Cheng Tsai; Ming-Dar Tsai; Yih-Jing Tang; Shuo-Tsung Chen; Li-Hsiang Wang (Journal of Medical and Biological Engineering, 2021)

The developmental regulator PatD modulates assembly of the cell‐division protein FtsZ in the cyanobacterium Anabaena sp. PCC 7120 - Li Wang; Tian‐Cai Niu; Ana Valladares; Gui‐Ming Lin; Ju‐Yuan Zhang; Antonia Herrero; Wen‐Li Chen; Cheng‐Cai Zhang (Environmental Microbiology, 2021)
Summary FtsZ is a tubulin‐like GTPase that polymerizes to initiate the process of cell division in bacteria. Heterocysts are terminally differentiated cells of filamentous cyanobacteria that have lost the capacity for cell division and in which the ftsZ gene is downregulated. However, mechanisms of FtsZ regulation during heterocyst differentiation have been scarcely investigated. The patD gene is NtcA dependent and involved in the optimization of heterocyst frequency in Anabaena sp. PCC 7120. Here, we report that the inactivation of patD caused the formation of multiple FtsZ‐rings in vegetative cells, cell enlargement, and the retention of peptidoglycan synthesis activity in heterocysts, whereas its ectopic expression resulted in aberrant FtsZ polymerization and cell division. PatD interacted with FtsZ, increased FtsZ precipitation in sedimentation assays, and promoted the formation of thick straight FtsZ bundles that differ from the toroidal aggregates formed by FtsZ alone. These results suggest that in the differentiating heterocysts, PatD interferes with the assembly of FtsZ. We propose that in Anabaena FtsZ is a bifunctional protein involved in both vegetative cell division and regulation of heterocyst differentiation. In the differentiating cells PatD‐FtsZ interactions appear to set an FtsZ activity that is insufficient for cell division but optimal to foster differentiation.

Phytoavailability, translocation and soil thresholds derivation of cadmium for food safety through soil-wheat (Triticum aestivum L.) system - Min Lu; Xuerui Cao; Qiang Lin; Bilal Hussain; Ying Feng; Zhenli He; Kyong Ju Kang; Xiaoe Yang (Environmental Science and Pollution Research, 2021)

Dynamic Anthropometrics of Preschool Children in Taiwan for Playground Equipment Designs - I-Fang Cheng; Chien-Ju Lin; Li-Chieh Kuo; Bih-Jen Hsue; Fong-Chin Su (Journal of Medical and Biological Engineering, 2021)

Enhanced treatment of shale gas fracturing waste fluid through plant-microbial synergism - Bo Shao; Xu Tan; Ju-Long Li; Mei He; Lei Tian; Wen-Jie Chen; Yan Lin (Environmental Science and Pollution Research, 2021)

Cryostructures and ground ice content in ice-rich permafrost area of the Qinghai-Tibet Plateau with Computed Tomography Scanning - Xing-wen Fan; Zhan-ju Lin; Ze-yong Gao; Xiang-lian Meng; Fu-jun Niu; Jing Luo; Guo-an Yin; Fu-jun Zhou; Ai-yu Lan (Journal of Mountain Science, 2021)

Interest-activity symptom severity predicts response to ketamine infusion in treatment-resistant depression - Mu-Hong Chen; Wei-Chen Lin; Hui-Ju Wu; Ya-Mei Bai; Cheng-Ta Li; Shih-Jen Tsai; Chen-Jee Hong; Pei-Chi Tu; Tung-Ping Su (Psychopharmacology, 2021)

Leaf spot of Sapindus mukorossi caused by Diaporthe biconispora in China - Yuan-Zhi Si; Jian-Wei Sun; De-Wei Li; Lin Huang; Yue Ju; Li-HuaZhu (Australasian Plant Pathology, 2021)

Reliability and Validity of a Mobile Device for Assessing Head Control Ability - Mohammad Nikkhoo; Chi-Chien Niu; Chen-Ju Fu; Meng-Ling Lu; Wen-Chien Chen; Yang-Hua Lin; Chih-Hsiu Cheng (Journal of Medical and Biological Engineering, 2021)

Associations of Serum Selenium Levels in the First Trimester of Pregnancy with the Risk of Gestational Diabetes Mellitus and Preterm Birth: a Preliminary Cohort Study - Peng Ju Liu; Aimin Yao; Liangkun Ma; Xiao Yan Chen; Song Lin Yu; Yanping Liu; Yi Xuan Hou (Biological Trace Element Research, 2021)

Syn-2, 3-diols and anti-inflammatory indole derivatives from Streptomyces sp. CB09001 - Lin Jiang; Hong Pu; Xiangjing Qin; Jianxin Liu; Zhongqing Wen; Yimin Huang; Jingxi Xiang; Yunxi Xiang; Jianhua Ju; Yanwen Duan; Yong Huang (Natural Product Research, 2021)

Analysis of Meteorological Drought Resilience and Risk Assessment of Groundwater Using Signal Analysis Method - Yuan-Chien Lin; En-Dian Kuo; Wan-Ju Chi (Water Resources Management, 2021)

Relationship of MDR1 gene polymorphism and P-glycoprotein expression in Chinese refractory lupus nephritis - Jun Zhou; Hua Lin; Ju Chen (Biologia, 2021)
To evaluate the association of multidrug resistance 1 ( MDR1 ) polymorphism and the expression of P-glycoprotein (Pgp) in Chinese refractory lupus nephritis (LN) patients. Polymerase chain reaction-direct sequencing was used to analyze MDR1 polymorphism. The genotype distribution of MDR1 polymorphism in 132 SLE (systemic lupus erythematosus) patients was evaluated. ELISA was used to measure the expression of Pgp. Relationship among Pgp expression, MDR1 polymorphism, SLEDAI (SLE disease activity index), and kidney pathological score was analyzed by using One-way ANOVA and Pearson linear correlation. The frequency distribution of the MDR1 gene was consistent with the Hardy-Weinberg equilibrium. Compared with CT and CC, patients with T/T homozygote in MDR1 C3435T had significantly increased Pgp expression in the refractory group ( p p p MDR1 C3435T polymorphism is significantly associated with Pgp expression in patients with refractory LN. Pgp expression is closely related to SLEDAI and renal pathological score. Thus, Pgp may be useful in evaluation of the prognosis of patients with refractory LN.

Improving Image Correlation and Differentiation of 3D Endoluminal Lesions in the Air Spaces Using a Novel Target Gray Level Mapping Technique: A Preliminary Study of Its Application to Computed Tomographic Colonography and Comparison with Traditional Surface Rendering Method - Lih-Shyang Chen; Ta-Wen Hsu; Shao-Jer Chen; Shu-Han Chang; Chih-Wen Lin; Yu-Ruei Chen; Chin-Chiang Hsieh; Shu-Chen Han; Ku-Yaw Chang; Chun-Ju Hou (Journal of Medical and Biological Engineering, 2020)

Greater promotion of DNRA rates and nrfA gene transcriptional activity by straw incorporation in alkaline than in acidic paddy soils - Ren Bai; Yun-Ting Fang; Liu-Ying Mo; Ju-Pei Shen; Lin-Lin Song; Ya-Qi Wang; Li-Mei Zhang; Ji-Zheng He (Soil Ecology Letters, 2020)

Diagnostic approaches and contribution of next-generation sequencing technologies in genomic investigation of Vibrio parahaemolyticus that caused acute hepatopancreatic necrosis disease (AHPND) - Lean Huat Yu; Cindy Shuan Ju Teh; Kien Pong Yap; Kwai Lin Thong (Aquaculture International, 2020)

The gut-microbiota-testis axis mediated by the activation of the Nrf2 antioxidant pathway is related to prepuberal steroidogenesis disorders induced by di-(2-ethylhexyl) phthalate - Tian-Xin Zhao; Yue-Xin Wei; Jun-Ke Wang; Lin-Dong Han; Mang Sun; Yu-Hao Wu; Lian-Ju Shen; Chun-Lan Long; Sheng-De Wu; Guang-Hui Wei (Environmental Science and Pollution Research, 2020)

Technology-side carbon abatement cost curves for China’s power generation sector - Lin-Ju Chen; Zhen-Hai Fang; Fei Xie; Hai-Kuo Dong; Yu-Heng Zhou (Mitigation and Adaptation Strategies for Global Change, 2020)

Nitrous oxide emissions from tea garden soil following the addition of urea and rapeseed cake - Jialuo Yu; Shan Lin; Muhammad Shaaban; Wenliang Ju; Linchuan Fang (Journal of Soils and Sediments, 2020)

Initial chest CT findings in COVID-19: correlation with clinical features - Zhu-jing Shen; Nan Lu; Lu-lu Gao; Jian Lv; Hua-fu Luo; Ji-feng Jiang; Chao Xu; Shi-ya Li; Ju-jiang Mao; Kai Li; Xiao-pei Xu; Bin Lin (Journal of Zhejiang University-SCIENCE B, 2020)

An integrated biophysical approach to discovering mechanisms of NDM-1 inhibition for several thiol-containing drugs - Sarah Fullington; Zishuo Cheng; Caitlyn Thomas; Callie Miller; Kundi Yang; Lin-Cheng Ju; Alexander Bergstrom; Ben A. Shurina; Stacey Lowery Bretz; Richard C. Page; David L. Tierney; Michael W. Crowder (JBIC Journal of Biological Inorganic Chemistry, 2020)

Two novel pleiotropic loci associated with osteoporosis and abdominal obesity - Lu Liu; Xiao-Lin Yang; Hong Zhang; Zi-Jia Zhang; Xin-Tong Wei; Gui-Juan Feng; Ju Liu; Hui-Ping Peng; Rong Hai; Hui Shen; Qing Tian; Hong-Wen Deng; et al. (Human Genetics, 2020)

Comprehensive Natural Environment and Landscape Signs in Coastal Settlement Hazard Assessment: Case of East Taiwan between the Coastal Mountain and the Pacific Ocean - Shyang-Woei Lin; Chia-Feng Yen; Chih-Hsin Chang; Li-Jin Wang; Hung-Ju Shih (Journal of Marine Science and Engineering, 2020)
In East Taiwan, coastal settlements are scattered and narrowly confined between the Coastal Mountain and the Pacific Ocean. These settlements are currently at risk as there is no room for retreat. Therefore, it is essential to conduct a comprehensive and continuous hazard assessment in these coastal residential areas. In order to avoid biased towards the natural environment, the factors that cannot easily be built within the geographic information system (GIS) database are distinguished by Unmanned Aerial Vehicle (UAV) to conduct a vulnerability assessment of threats to coastal zones. The method: we used the east coast of Taiwan as an example, through GIS and statistical analysis in land-use status, vulnerable population groups and UAV landscape signs of indicators of erosion and accumulation. Through the main output of an intuition scatter map, the erosion landscape susceptibility, economical land-use exposure, and special population groups’ ratio allowed for the easy comparison of the vulnerability, risk level and resilience between different coastal settlements. These diverse observation aspects of risk assessment results can provide prevention and control strategies that meet the different needs of coastal risk management in restricting and strengthening the land-use development of communities.

Correction to: Development of recombinase polymerase amplification assay for rapid detection of Meloidogyne incognita, M. javanica, M. arenaria, and M. enterolobii - Yuliang Ju; Yu Lin; Guogen Yang; Huiping Wu; Yuemin Pan (European Journal of Plant Pathology, 2020)

Association between tooth loss and gray matter volume in cognitive impairment - Chia-Shu Lin; Hsiao-Han Lin; Shin-Woei Fann; Wei-Ju Lee; Ming-Lun Hsu; Shuu-Jiun Wang; Jong-Ling Fuh (Brain Imaging and Behavior, 2020)

Advances in Urban Meteorological Research in China - Shiguang Miao; Weimei Jiang; Ping Liang; Hongnian Liu; Xuemei Wang; Jianguo Tan; Ning Zhang; Ju Li; Wupeng Du; Lin Pei (Journal of Meteorological Research, 2020)

Optimization of the OCO-2 Cloud Screening Algorithm and Evaluation against MODIS and TCCON Measurements over Land Surfaces in Europe and Japan - Sijie Chen; Shuaibo Wang; Lin Su; Changzhe Dong; Ju Ke; Zhuofan Zheng; Chonghui Cheng; Bowen Tong; Dong Liu (Advances in Atmospheric Sciences, 2020)

Molecular characterization of extended-spectrum β-lactamase-producing Klebsiella pneumoniae from a Malaysian hospital - Golnaz Mobasseri; Kwai Lin Thong; Ganeswarie Rajasekaram; Cindy Shuan Ju Teh (Brazilian Journal of Microbiology, 2020)

Strictly Lobar Cerebral Microbleeds Are Associated with Increased White Matter Volume - Pei-Ning Wang; Kun-Hsien Chou; Li-Ning Peng; Li-Kuo Liu; Wei-Ju Lee; Liang-Kung Chen; Ching-Po Lin; Chih-Ping Chung (Translational Stroke Research, 2020)

Allelopathy confers an invasive Wedelia higher resistance to generalist herbivore and pathogen enemies over its native congener - Shan-Shan Qi; Yan-Jie Liu; Zhi-Cong Dai; Ling-Yun Wan; Dao-Lin Du; Rui-Ting Ju; Justin S. H. Wan; Stephen P. Bonser (Oecologia, 2020)

Gallic Acid Attenuated LPS-Induced Neuroinflammation: Protein Aggregation and Necroptosis - Yu-Ling Liu; Chia-Chi Hsu; Hui-Ju Huang; Chih-Jung Chang; Shu-Hui Sun; Anya Maan-Yuh Lin (Molecular Neurobiology, 2020)

Anti-inflammatory Effect of AZD6244 on Acrolein-Induced Neuroinflammation - Wen-Chien Ho; Chia-Chi Hsu; Hui-Ju Huang; Hsiang-Tsui Wang; Anya Maan-Yuh Lin (Molecular Neurobiology, 2020)

Role of coaggregation in the pathogenicity and prolonged colonisation of Vibrio cholerae - Yien Shin Toh; Soo Ling Yeoh; Ivan Kok Seng Yap; Cindy Shuan Ju Teh; Thin Thin Win; Kwai Lin Thong; Chun Wie Chong (Medical Microbiology and Immunology, 2019)

Development of recombinase polymerase amplification assay for rapid detection of Meloidogyne incognita, M. javanica, M. arenaria, and M. enterolobii - Yuliang Ju; Yu Lin; Guogen Yang; Huiping Wu; Yuemin Pan (European Journal of Plant Pathology, 2019)

Transcriptome analysis of rice-seedling roots under soil–salt stress using RNA-Seq method - Anil Kumar Nalini Chandran; Jeong-Won Kim; Yo-Han Yoo; Hye Lin Park; Yeon-Ju Kim; Man-Ho Cho; Ki-Hong Jung (Plant Biotechnology Reports, 2019)

Indication of dynamic neurovascular coupling from inconsistency between EEG and fMRI indices across sleep–wake states - Changwei W. Wu; Pei-Jung Tsai; Sharon Chia-Ju Chen; Chia-Wei Li; Ai-Ling Hsu; Hong-Yi Wu; Yu-Ting Ko; Pai-Chuan Hung; Chun-Yen Chang; Ching-Po Lin; Timothy J. Lane; Chia-Yuen Chen (Sleep and Biological Rhythms, 2019)

Anthropometric Database of the Preschool Children from 2 to 6 Years in Taiwan - I-Fang Cheng; Li-Chieh Kuo; Chien-Ju Lin; Hsiao-Feng Chieh; Fong-Chin Su (Journal of Medical and Biological Engineering, 2019)

High Circulatory Phosphate Level Is Associated with Cerebral Small-Vessel Diseases - Chih-Ping Chung; Li-Ning Peng; Kun-Hsien Chou; Li-Kuo Liu; Wei-Ju Lee; Ching-Po Lin; Liang-Kung Chen; Pei-Ning Wang (Translational Stroke Research, 2019)

Health risk of metal exposure via inhalation of cigarette sidestream smoke particulate matter - Li-Chuan Cheng; Chun-Ju Lin; Huei-Ju Liu; Lih-Ann Li (Environmental Science and Pollution Research, 2019)

Mitochondrial Genetic Diversity of the Freshwater Snail Melanoides tuberculata - Yuh-Wen Chiu; Ye-Chen Gan; Po-Hsun Kuo; Kui-Ching Hsu; Mian-Shin Tan; Yu-Min Ju; Hung-Du Lin (Biochemical Genetics, 2019)

Neonatal Dexamethasone Treatment Suppresses Hippocampal Estrogen Receptor α Expression in Adolescent Female Rats - Hui-Fang Chiu; Michael W. Y. Chan; Chiung-Yin Cheng; Jian-Liang Chou; Jora Meng-Ju Lin; Yi-Ling Yang; Kwok-Tung Lu (Molecular Neurobiology, 2019)

Far-infrared Radiation Improves Motor Dysfunction and Neuropathology in Spinocerebellar Ataxia Type 3 Mice - Shin-Wu Liu; Jui-Chih Chang; Sheng-Fei Chuang; Ko-Hung Liu; Wen-Ling Cheng; Hui-Ju Chang; Huei-Shin Chang; Ta-Tsung Lin; Ching-Liang Hsieh; Wei-Yong Lin; Mingli Hsieh; Shou-Jen Kuo; et al. (The Cerebellum, 2019)

Interhemispheric functional connectivity for Alzheimer’s disease and amnestic mild cognitive impairment based on the triple network model - Zheng-luan Liao; Yun-fei Tan; Ya-ju Qiu; Jun-peng Zhu; Yan Chen; Si-si Lin; Ming-hao Wu; Yan-ping Mao; Jiao-jiao Hu; Zhong-xiang Ding; En-yan Yu (Journal of Zhejiang University-SCIENCE B, 2018)

Activation of histamine H4 receptor suppresses the proliferation and invasion of esophageal squamous cell carcinoma via both metabolism and non-metabolism signaling pathways - Gong-Hao He; Jia-Qi Ding; Xin Zhang; Wen-Mang Xu; Xiao-Qian Lin; Mei-Jin Huang; Ju Feng; Ping Wang; Wen-Ke Cai (Journal of Molecular Medicine, 2018)

The Divalent Elements Changes in Early Stages of Chronic Kidney Disease - Wan-Ju Kung; Ching-Tang Shih; Chien-Hung Lee; Ching-Chiang Lin (Biological Trace Element Research, 2018)

Design, synthesis, and biological evaluation of Cyclobentinib (CB1107) as a potential anti-CML agent - Zijun Zhou; Yang Wang; Jun Li; Baichun Hu; Xiaolin Lin; Ye Chen; Rui Wang; Ju Liu; Hongsheng Liu (Medicinal Chemistry Research, 2018)

Late Pleistocene aeolian activity in Haitan Island, Southeast China: Insights from optically stimulated luminescence dating of coastal dunes on marine terraces - Jian-hui Jin; Zhi-zhong Li; Yan Cheng; Xiao-lin Xu; Zhi-xing Li; Xiao-ju Liu (Journal of Mountain Science, 2018)

Immunogenicity of adenovirus and DNA vaccines co-expressing P39 and lumazine synthase proteins of Brucella abortus in BALB/c mice - Guo-Zhen Lin; Ju-Tian Yang; Suo-Cheng Wei; Shi-En Chen; Sheng-Dong Huo; Zhong-Ren Ma (Tropical Animal Health and Production, 2018)

D-Cycloserine Ameliorates Autism-Like Deficits by Removing GluA2-Containing AMPA Receptors in a Valproic Acid-Induced Rat Model - Han-Fang Wu; Po See Chen; Ya-Ting Hsu; Chi-Wei Lee; Tzu-Feng Wang; Yi-Ju Chen; Hui-Ching Lin (Molecular Neurobiology, 2018)

Variations in the northern permafrost boundary over the last four decades in the Xidatan region, Qinghai–Tibet Plateau - Jing Luo; Fu-jun Niu; Zhan-ju Lin; Ming-hao Liu; Guo-an Yin (Journal of Mountain Science, 2018)

Gracilibacillus eburneus sp.nov., a moderately halophilic bacterium isolated from Xinjiang province, China - Hui-Lin Guan; Yun-Jiao Zhang; Xiao-Ju Lu; Man Jia; Zheng-Yun Zhang; Xu-Hong Gao; Yong-Chun Ma; Fei Tian; Shu-Kun Tang (Archives of Microbiology, 2018)

Sediment control function of river notches - Chia-Hsing Lin; Cheng-Ju Liu; Shih-Hsun Lin; Chjeng-Lun Shieh (Journal of Mountain Science, 2018)

Neuroprotective Effects of Baicalein on Acrolein-induced Neurotoxicity in the Nigrostriatal Dopaminergic System of Rat Brain - Wei-Zhong Zhao; Hsiang-Tsui Wang; Hui-Ju Huang; Yu-Li Lo; Anya Maan-Yuh Lin (Molecular Neurobiology, 2018)

Soluble Epoxide Hydrolase Inhibition Attenuates MPTP-Induced Neurotoxicity in the Nigrostriatal Dopaminergic System: Involvement of α-Synuclein Aggregation and ER Stress - Hui-Ju Huang; Yi-Ting Wang; Hui-Ching Lin; Yi-Hsuan Lee; Anya Maan-Yuh Lin (Molecular Neurobiology, 2018)

Alleviation of N-Methyl-d-Aspartate Receptor-Dependent Long-Term Depression via Regulation of the Glycogen Synthase Kinase-3β Pathway in the Amygdala of a Valproic Acid-Induced Animal Model of Autism - Han-Fang Wu; Po See Chen; Yi-Ju Chen; Chi-Wei Lee; I-Tuan Chen; Hui-Ching Lin (Molecular Neurobiology, 2017)

Histopathological changes in zebrafish embryos exposed to DLPCBs extract from Zhanjiang coastal sediment - Yunpeng Yu; Fanghong Nie; Anthony Hay; Hongying Lin; Yi Ma; Xianghong Ju; Dongliang Gong; Jinjun Chen; Ravi Gooneratne (Environmental Monitoring and Assessment, 2017)

Midgut morphological changes and autophagy during metamorphosis in sand flies - Juliana Malta; Matthew Heerman; Ju Lin Weng; Kenner M. Fernandes; Gustavo Ferreira Martins; Marcelo Ramalho-Ortigão (Cell and Tissue Research, 2017)

EGFL7-overexpressing epidermal stem cells promotes fibroblast proliferation and migration via mediating cell adhesion and strengthening cytoskeleton - Rong-Hua Yang; Shao-Hai Qi; Shu-Bin Ruan; Ze-Peng Lin; Yan Lin; Feng-Gang Zhang; Xiao-Dong Chen; Ju-Lin Xie (Molecular and Cellular Biochemistry, 2016)

Strength, Deformability and X-ray Micro-CT Observations of Deeply Buried Marble Under Different Confining Pressures - Sheng-Qi Yang; Yang Ju; Feng Gao; Yi-Lin Gui (Rock Mechanics and Rock Engineering, 2016)

Paleohydrological processes revealed by n-alkane δD in lacustrine sediments of Lake Pumoyum Co, southern Tibetan Plateau, and their response to climate changes during the past 18.5 cal ka - Yong Wang; Liping Zhu; Junbo Wang; Jianting Ju; Ping Peng; Xiao Lin; Jianfang Hu; Mitsugu Nishimura (Journal of Paleolimnology, 2016)

In vitro anti-tumor activity of the tanshinone IIA against SKOV3 cells - Ju Huang; Hao Lin; YingKai Hong (Natural Product Research, 2016)

Microbial community in a multi-trophic aquaculture system of Apostichopus japonicus, Styela clava and microalgae - Jian Lin; Bao Ju; Yanan Yao; Xiaoming Lin; Ronglian Xing; Li Teng; Aili Jiang (Aquaculture International, 2016)

Chidamide alleviates TGF-β-induced epithelial–mesenchymal transition in lung cancer cell lines - Sheng-Hao Lin; Bing-Yen Wang; Ching-Hsiung Lin; Peng-Ju Chien; Yueh-Feng Wu; Jiunn-Liang Ko; Jeremy J. W. Chen (Molecular Biology Reports, 2016)

Design of wireless multi-parameter monitoring system for oral feeding of premature infants - Yu-Lin Wang; Hsing-Chien Kuo; Lin-Yu Wang; Mei-Ju Ko; Bor-Shyh Lin (Medical & Biological Engineering & Computing, 2016)

Performance comparison of permafrost models in Wudaoliang Basin, Qinghai-Tibet Plateau, China - Guo-an Yin; Fu-jun Niu; Zhan-ju Lin; Jing Luo; Ming-hao Liu (Journal of Mountain Science, 2016)

Molecular characterization of melanin-concentrating hormone (MCH) in Schizothorax prenanti: cloning, tissue distribution and role in food intake regulation - Tao Wang; Dengyue Yuan; Chaowei Zhou; Fangjun Lin; Rongbin Wei; Hu Chen; Hongwei Wu; Zhiming Xin; Ju Liu; Yundi Gao; Defang Chen; Shiyong Yang; et al. (Fish Physiology and Biochemistry, 2016)

Genetic diversity analysis of Jatropha curcas L. accessions cultivated in Taiwan using inter simple sequence repeats (ISSR) markers - Celimphilo Mavuso; Yong-Pei Wu; Fure-Chyi Chen; Bing-Hong Huang; Su-Ju Lin (Agroforestry Systems, 2016)

Prevalence of potential nitrogen‐fixing, green sulfur bacteria in the skeleton of reef‐building coral I sopora palifera - Shan‐Hua Yang; Sonny T. M. Lee; Chang‐Rung Huang; Ching‐Hung Tseng; Pei‐Wen Chiang; Chung‐Pin Chen; Hsing‐Ju Chen; Sen‐Lin Tang (Limnology and Oceanography, 2016)
Microbial endoliths, which inhabit interior pores of rocks, skeletons and coral, are ubiquitous in terrestrial and marine environments. In this study, various colored layers stratified the endolithic environment within the skeleton of Isopora palifera ; however, there was a distinct green‐pigmented layer in the skeleton (beneath the living coral tissue). To characterize diversity of endolithic microorganisms, 16S ribosomal RNA gene amplicon pyrosequencing was used to investigate bacterial communities in the green layer of eight I. palifera coral colonies retrieved from two locations on Green Island, Taiwan. The dominant bacterial group in the green layer belonged to the bacterial phylum Chlorobi, green sulfur bacteria capable of anoxygenic photosynthesis and nitrogen fixation. Specifically, bacteria of the genus Prosthecochloris were dominant in this green layer. To our knowledge, this is the first study to provide a detailed profile of endolithic bacteria in coral and to determine the prevalence of Prosthecochloris in the green layer. Based on our findings, we infer that these bacteria may have an important functional role in the coral holobiont in the nutrient‐limited coral reef ecosystem.

Pollen and seed flow under different predominant winds in wind-pollinated and wind-dispersed species Engelhardia roxburghiana - Zheng-Feng Wang; Ju-Yu Lian; Wan-Hui Ye; Hong-Lin Cao; Qian-Mei Zhang; Zhang-Ming Wang (Tree Genetics & Genomes, 2016)

Poly(lactic-co-glycolide) polymer constructs cross-linked with human BMP-6 and VEGF protein significantly enhance rat mandible defect repair - Anusuya Das; Brian A. Fishero; J. Jared Christophel; Ching-Ju Li; Nikita Kohli; Yong Lin; Abhijit S. Dighe; Quanjun Cui (Cell and Tissue Research, 2016)

Involvement of NADPH oxidases and non-muscle myosin light chain in senescence of endothelial progenitor cells in hyperlipidemia - Ting-Bo Li; Jie-Jie Zhang; Bin Liu; Wei-Qi Liu; Yan Wu; Xiao-Ming Xiong; Xiu-Ju Luo; Qi-Lin Ma; Jun Peng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)

Naringenin Suppresses Neuroinflammatory Responses Through Inducing Suppressor of Cytokine Signaling 3 Expression - Ling-Hsuan Wu; Chingju Lin; Hsiao-Yun Lin; Yu-Shu Liu; Caren Yu-Ju Wu; Cheng-Fang Tsai; Pei-Chun Chang; Wei-Lan Yeh; Dah-Yuu Lu (Molecular Neurobiology, 2016)

Clinical Pedicle Screw Insertion Trials and System Improvement of C-arm Image Navigation System - Chih-Ju Chang; Ching-Hsiao Yu; Geng-Li Lin; Alex Tse; Hong-Yu Chu; Ching-Shiow Tseng (Journal of Medical and Biological Engineering, 2016)

Ya-fish (Schizothorax prenanti) spexin: identification, tissue distribution and mRNA expression responses to periprandial and fasting - Hongwei Wu; Fangjun Lin; Hu Chen; Ju Liu; Yundi Gao; Xin Zhang; Jin Hao; Defang Chen; Dengyue Yuan; Tao Wang; Zhiqiong Li (Fish Physiology and Biochemistry, 2016)

New phenyl derivatives from endophytic fungus Botryosphaeria sp. SCSIO KcF6 derived of mangrove plant Kandelia candel - Zhi-ran Ju; Xiaochu Qin; Xiu-ping Lin; Jun-feng Wang; Kumaravel Kaliyaperumal; Yong-qi Tian; Juan Liu; Fen Liu; Zhengchao Tu; Shi-hai Xu; Yonghong Liu (Natural Product Research, 2016)

Prenatal molecular cytogenetic analysis of a mild dysmorphic fetus with a huge unbalance karyotype involving partial 9p deletion and partial 18q duplication - Yueh-Chun Li; Yi-Ju Pan; Fuu-Jen Tsai; Chyi-Chyang Lin (Genes & Genomics, 2016)

Development of single-chain variable fragments (scFv) against influenza virus targeting hemagglutinin subunit 2 (HA2) - Tai-Wei Li; Shu-Fang Cheng; Yen-Tzu Tseng; Yu-Chih Yang; Wen-chun Liu; Sheng-Cyuan Wang; Mei-Ju Chou; Yu-Jen Lin; Yueh Wang; Pei-Wen Hsiao; Suh-Chin Wu; Ding-Kwo Chang (Archives of Virology, 2016)

RETRACTED ARTICLE: Effects of Repetitive Transcranial Magnetic Stimulation on Cognitive Impairment in Stroke Patients: A Meta-Analysis - Lei Cao; Rui Zhao; Su Huo; Ju-Bao Du; Lin Liu; Yan-Ming Zhang; Wei-Qun Song (Molecular Neurobiology, 2015)

Impact of short-term climate variation and hydrology change on thermal structure and water quality of a canyon-shaped, stratified reservoir - Wei-Xing Ma; Ting-Lin Huang; Xuan Li; Hai-Han Zhang; Tuo Ju (Environmental Science and Pollution Research, 2015)

MicroRNA-134 modulates resistance to doxorubicin in human breast cancer cells by downregulating ABCC1 - Lin Lu; Fang Ju; Hui Zhao; Xuezhen Ma (Biotechnology Letters, 2015)

Genome characterization and phylogenetic analysis of a lineage IV peste des petits ruminants virus in southern China - Xiao-Peng Li; Shao-Lun Zhai; Dong-Sheng He; Peng-Ju Guo; Dian-Hong Lv; Xiao-Hui Wen; Man-Lin Luo; Rui-Ai Chen; Wen-Kang Wei (Virus Genes, 2015)

Aryl hydrocarbon receptor agonists upregulate VEGF secretion from bronchial epithelial cells - Ming-Ju Tsai; Tsu-Nai Wang; Yi-Shiuan Lin; Po-Lin Kuo; Ya-Ling Hsu; Ming-Shyan Huang (Journal of Molecular Medicine, 2015)

Protective effects of aloperine on neonatal rat primary cultured hippocampal neurons injured by oxygen–glucose deprivation and reperfusion - Ning-Tian Ma; Ru Zhou; Ren-Yuan Chang; Yin-Ju Hao; Lin Ma; Shao-Ju Jin; Juan Du; Jie Zheng; Cheng-Jun Zhao; Yang Niu; Tao Sun; Wei Li; et al. (Journal of Natural Medicines, 2015)

Effects of elevated carbon dioxide concentration on nitrous oxide emissions and nitrogen dynamics in a winter-wheat cropping system in northern China - Yingchun Li; Erda Lin; Xue Han; Zhengping Peng; Wen Wang; Xingyu Hao; Hui Ju (Mitigation and Adaptation Strategies for Global Change, 2015)

Inhibition of myosin light chain kinase reduces NADPH oxidase-mediated oxidative injury in rat brain following cerebral ischemia/reperfusion - Hong-Feng Zhang; Ting-Bo Li; Bin Liu; Zheng Lou; Jie-Jie Zhang; Jing-Jie Peng; Xiao-Jie Zhang; Qi-Lin Ma; Jun Peng; Xiu-Ju Luo (Naunyn-Schmiedeberg's Archives of Pharmacology, 2015)

Environmental stochasticity promotes copper bioaccumulation and bioenergetic response in tilapia - Wei-Yu Chen; Yun-Ru Ju; Chia-Jung Lin; Jeng-Wei Tsai; Szu-Cheih Chen; Chung-Min Liao (Stochastic Environmental Research and Risk Assessment, 2015)

Vascular smooth muscle cell differentiation to an osteogenic phenotype involves matrix metalloproteinase-2 modulation by homocysteine - Tingjiao Liu; Jinghan Lin; Ting Ju; Lei Chu; Liming Zhang (Molecular and Cellular Biochemistry, 2015)

Host shoot clipping depresses the growth of weedy hemiparasitic Pedicularis kansuensis - Xiao-Lin Sui; Wei Huang; Yun-Ju Li; Kai-Yun Guan; Ai-Rong Li (Journal of Plant Research, 2015)

Pectobacterium chrysanthemi as the dominant causal agent of bacterial soft rot in Oncidium “Grower Ramsey” - Yi-Hsien Lin; Pei-Ju Lee; Wan-Ting Shie; Lih-Ling Chern; Yung-Chun Chao (European Journal of Plant Pathology, 2015)

Ascomycotin A, a new citromycetin analogue produced by Ascomycota sp. Ind19F07 isolated from deep sea sediment - Yong-qi Tian; Xiu-ping Lin; Juan Liu; Kumaravel Kaliyaperumal; Wen Ai; Zhi-ran Ju; Bin Yang; Junfeng Wang; Xian-wen Yang; Yonghong Liu (Natural Product Research, 2015)

EGFR mediates docetaxel resistance in human castration-resistant prostate cancer through the Akt-dependent expression of ABCB1 (MDR1) - Tzyh-Chyuan Hour; Shiu-Dong Chung; Wang-Yi Kang; Ying-Chu Lin; Shu-Ju Chuang; A-Mei Huang; Wen-Jeng Wu; Shu-Pin Huang; Chao-Yuan Huang; Yeong-Shiau Pu (Archives of Toxicology, 2015)

Increase of Zinc Finger Protein 179 in Response to CCAAT/Enhancer Binding Protein Delta Conferring an Antiapoptotic Effect in Astrocytes of Alzheimer’s Disease - Shao-Ming Wang; Yi-Chao Lee; Chiung-Yuan Ko; Ming-Derg Lai; Ding-Yen Lin; Ping-Chieh Pao; Jhih-Ying Chi; Yu-Wei Hsiao; Tsung-Lin Liu; Ju-Ming Wang (Molecular Neurobiology, 2015)

Is abnormal non-high-density lipoprotein cholesterol a gender-specific predictor for metabolic syndrome in patients with schizophrenia taking second-generation antipsychotics? - Esther Ching-Lan Lin; Wen-Chuan Shao; Hsin-Ju Yang; Miaofen Yen; Sheng-Yu Lee; Pei-Chun Wu; Ru-Band Lu (Metabolic Brain Disease, 2015)

Prevention of natural flowering in pineapple (Ananas comosus) by shading and urea application - Meng-Tzu Lin; Alfred Ming Chen; Tzong-Shyan Lin; Ching-San Kuan; Ching-Lung Lee; Wen-Ju Yang (Horticulture, Environment, and Biotechnology, 2015)

Integrated assessment of China’s agricultural vulnerability to climate change: a multi-indicator approach - Yingchun Li; Wei Xiong; Wei Hu; Pam Berry; Hui Ju; Erda Lin; Wen Wang; Kuo Li; Jie Pan (Climatic Change, 2015)

Integrated assessment of China’s adaptive capacity to climate change with a capital approach - Minpeng Chen; Fu Sun; Pam Berry; Rob Tinch; Hui Ju; Erda Lin (Climatic Change, 2015)

Greenhouse gas intensity of three main crops and implications for low-carbon agriculture in China - Wen Wang; Liping Guo; Yingchun Li; Man Su; Yuebin Lin; Christian de Perthuis; Xiaotang Ju; Erda Lin; Dominic Moran (Climatic Change, 2015)

Epigenetic Enhancement of Brain-Derived Neurotrophic Factor Signaling Pathway Improves Cognitive Impairments Induced by Isoflurane Exposure in Aged Rats - MuHuo Ji; Lin Dong; Min Jia; WenXue Liu; MingQiang Zhang; LinSha Ju; JiaoJiao Yang; Zhongcong Xie; JianJun Yang (Molecular Neurobiology, 2014)

Development, characterization and cross-species amplification of new microsatellite primers from an endemic species Cinnamomum kanehirae (Lauraceae) in Taiwan - Kuo-Hsiang Hung; Chia-Hung Lin; Huei-Chuan Shih; Yu-Chung Chiang; Li-Ping Ju (Conservation Genetics Resources, 2014)

Pore structure effect on reservoir electrical properties and well logging evaluation - Huan-Lin Bian; Ju Guan; Zhi-Qiang Mao; Xiao-Dong Ju; Gui-Qing Han (Applied Geophysics, 2014)

2.5D induced polarization forward modeling using the adaptive finite-element method - Yi-Xin Ye; Yu-Guo Li; Ju-Zhi Deng; Ze-Lin Li (Applied Geophysics, 2014)

Motor skill learning enhances the expression of activity-regulated cytoskeleton-associated protein in the rat cerebellum - Dean-Chuan Wang; Yu-Yi Lin; Tsan-Ju Chen; Hwai-Ting Lin (Journal of Comparative Physiology A, 2014)

SLDP: a Novel Protein Related to Caleosin Is Associated with the Endosymbiotic Symbiodinium Lipid Droplets from Euphyllia glabrescens - Buntora Pasaribu; I-Ping Lin; Jason T. C. Tzen; Guang-Yuh Jauh; Tung-Yung Fan; Yu-Min Ju; Jing-O Cheng; Chii-Shiarng Chen; Pei-Luen Jiang (Marine Biotechnology, 2014)

Schizothorax prenanti corticotropin-releasing hormone (CRH): molecular cloning, tissue expression, and the function of feeding regulation - Tao Wang; Chaowei Zhou; Dengyue Yuan; Fangjun Lin; Hu Chen; Hongwei Wu; Rongbin Wei; Zhiming Xin; Ju Liu; Yundi Gao; Zhiqiong Li (Fish Physiology and Biochemistry, 2014)

Protective effect of vitexin compound B-1 against hypoxia/reoxygenation-induced injury in differentiated PC12 cells via NADPH oxidase inhibition - Zhong-Bao Yang; Bin Tan; Ting-Bo Li; Zheng Lou; Jun-Lin Jiang; Ying-Jun Zhou; Jie Yang; Xiu-Ju Luo; Jun Peng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2014)

Long-term monitoring and modeling of polychlorinated dibenzo-p-dioxins and dibenzofurans from municipal solid waste incinerators and surrounding area in northern Taiwan - Hsiao-Hsuan Mi; Wan-Ju Wang; Sheng-Lun Lin; Yi-Chieh Lai; John Kennedy Mwangi; Lin Chi Wang; Guo-Ping Chang-Chien (Environmental Science and Pollution Research, 2014)

Nontidal sea level changes in Hiroshima Bay, Japan - Chuanzheng Zhang; Arata Kaneko; Xiaohua Zhu; Ju Lin (Acta Oceanologica Sinica, 2014)

Down-regulation of Gli-1 inhibits hepatocellular carcinoma cell migration and invasion - Jing-Song Chen; Hua-Shu Li; Jiong-Qiang Huang; Long-Juan Zhang; Xi-Lin Chen; Qian Wang; Jian Lei; Ju-Tao Feng; Qin Liu; Xiao-Hui Huang (Molecular and Cellular Biochemistry, 2014)

Aryl hydrocarbon receptor (AhR) agonists increase airway epithelial matrix metalloproteinase activity - Ming-Ju Tsai; Ya-Lin Hsu; Tsu-Nai Wang; Ling-Yu Wu; Chi-Tun Lien; Chih-Hsing Hung; Po-Lin Kuo; Ming-Shyan Huang (Journal of Molecular Medicine, 2014)

c-Src/Jak2/PDGFR/PKCδ-Dependent MMP-9 Induction Is Required for Thrombin-Stimulated Rat Brain Astrocytes Migration - Chih-Chung Lin; I-Ta Lee; Pei-Ling Chi; Hsi-Lung Hsieh; Shin-Ei Cheng; Li-Der Hsiao; Chiung-Ju Liu; Chuen-Mao Yang (Molecular Neurobiology, 2014)

Temporal characteristics of black carbon concentrations and its potential emission sources in a southern Taiwan industrial urban area - Yu-Hsiang Cheng; Chi-Chi Lin; Jyh-Jian Liu; Cheng-Ju Hsieh (Environmental Science and Pollution Research, 2014)

Changes in land use and agricultural production structure before and after the implementation of grain for green program in Western China — taking two typical counties as examples - Ping Zhou; An-bang Wen; Dong-chun Yan; Zhong-lin Shi; Jin Guo; Zhan-sheng Ju; Yi-lan Zhang (Journal of Mountain Science, 2014)

Genome-wide annotation, expression profiling, and protein interaction studies of the core cell-cycle genes in Phalaenopsis aphrodite - Hsiang-Yin Lin; Jhun-Chen Chen; Miao-Ju Wei; Yi-Chen Lien; Huang-Hsien Li; Swee-Suak Ko; Zin-Huang Liu; Su-Chiung Fang (Plant Molecular Biology, 2014)

Alda-1 reduces cerebral ischemia/reperfusion injury in rat through clearance of reactive aldehydes - Si-Hai Fu; Hong-Feng Zhang; Zhong-Bao Yang; Ting-Bo Li; Bin Liu; Zheng Lou; Qi-Lin Ma; Xiu-Ju Luo; Jun Peng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2014)

Thrombin Mediates Migration of Rat Brain Astrocytes via PLC, Ca2+, CaMKII, PKCα, and AP-1-Dependent Matrix Metalloproteinase-9 Expression - Chih-Chung Lin; I-Ta Lee; Wen-Bin Wu; Chiung-Ju Liu; Hsi-Lung Hsieh; Li-Der Hsiao; Chien-Chung Yang; Chuen-Mao Yang (Molecular Neurobiology, 2013)

Development of Cre–loxP technology in zebrafish to study the regulation of fish reproduction - Heng-Ju Lin; Shu-Hua Lee; Jen-Leih Wu; Yeh-Fang Duann; Jyh-Yih Chen (Fish Physiology and Biochemistry, 2013)

Comprehensive screening for multi-class veterinary drug residues and other contaminants in muscle using column-switching UPLC-MS/MS - Jia Zhan; Di-ming Xu; Shi-jie Wang; Ji Sun; Yin-jun Xu; Mei-lin Ni; Ju-yi Yin; Jie Chen; Xue-jun Yu; Zhi-qiang Huang (Food Additives & Contaminants: Part A, 2013)

APRIL depletion induces cell cycle arrest and apoptosis through blocking TGF-β1/ERK signaling pathway in human colorectal cancer cells - Feng Wang; Lin Chen; Hongbin Ni; Guihua Wang; Weifeng Ding; Hui Cong; Shaoqing Ju; Shumei Yang; Huimin Wang (Molecular and Cellular Biochemistry, 2013)

Menstrual blood-derived mesenchymal stem cells differentiate into functional hepatocyte-like cells - Xiao-zhou Mou; Jian Lin; Jin-yang Chen; Yi-fei Li; Xiao-xing Wu; Bing-yu Xiang; Cai-yun Li; Ju-ming Ma; Charlie Xiang (Journal of Zhejiang University-SCIENCE B, 2013)

Immunologic Mechanism of Patchouli Alcohol Anti-H1N1 Influenza Virus May Through Regulation of the RLH Signal Pathway In Vitro - Xian-Lin Wu; Da-Hong Ju; Jia Chen; Bin Yu; Kang-Li Liu; Jin-Xiong He; Cong-Qi Dai; Sha Wu; Zhou Chang; You-Ping Wang; Xiao-Yin Chen (Current Microbiology, 2013)

The impacts of climate change on agricultural production systems in China - Hui Ju; Marijn van der Velde; Erda Lin; Wei Xiong; Yingchun Li (Climatic Change, 2013)

Rural livelihoods and climate variability in Ningxia, Northwest China - Yue Li; D. Conway; Yanjuan Wu; Qingzhu Gao; S. Rothausen; Wei Xiong; Hui Ju; Erda Lin (Climatic Change, 2013)

The Transurethral Seminal Vesiculoscopy in the Diagnosis and Treatment of the Seminal Vesicle Disease - Cong-hui Han; Qing Liang; Bing-zheng Dong; Lin Hao; Tao Fan; Jun-jie Zhang; Wen-da Zhang; Bo Chen; Xiang-zheng Qiu; Xiang-ju Zhou; Chang-song Pei (Cell Biochemistry and Biophysics, 2013)

Isolation and characterization of novel ginsenoside-hydrolyzing glycosidase from Microbacterium esteraromaticum that transforms ginsenoside Rb2 to rare ginsenoside 20(S)-Rg3 - Lin-Hu Quan; Chao Wang; Yan Jin; Ting-Rui Wang; Yeon-Ju Kim; Deok Chun Yang (Antonie van Leeuwenhoek, 2013)

Microbial transformation of ginsenoside Rb1 to compound K by Lactobacillus paralimentarius - Lin-Hu Quan; Yeon-Ju Kim; Guan Hao Li; Kwang-Tea Choi; Deok-Chun Yang (World Journal of Microbiology and Biotechnology, 2013)

Geochemistry of ultramafic xenoliths in Cenozoic alkali basalts from Jiangsu province, eastern China and their geological implication - SHAO-WEI HUANG; YUNG-TAN LEE; JU-CHIN CHEN; KUNG-SUAN HO; MENG-LUNG LIN; YEN-TSUI HU; REN-YI HUANG (Journal of Earth System Science, 2013)

Effect of two maximal isometric contractions on eccentric exercise-induced muscle damage of the elbow flexors - Trevor C. Chen; Hsin-Lian Chen; Ming-Ju Lin; Che-Hsiu Chen; Alan J. Pearce; Kazunori Nosaka (European Journal of Applied Physiology, 2013)

Tail loss compromises immunity in the many-lined skink, Eutropis multifasciata - Chi-Chien Kuo; Chiou-Ju Yao; Te-En Lin; Hsu-Che Liu; Yu-Cheng Hsu; Ming-Kun Hsieh; Wen-San Huang (The Science of Nature, 2013)

Genome-wide association study identified novel genetic variant on SLC45A3 gene associated with serum levels prostate-specific antigen (PSA) in a Chinese population - Jielin Sun; Sha Tao; Yong Gao; Tao Peng; Aihua Tan; Haiying Zhang; Xiaobo Yang; Xue Qin; Yanling Hu; Junjie Feng; Seong-Tae Kim; Xiaoling Lin; et al. (Human Genetics, 2013)

Lipopolysaccharide/adenosine triphosphate-mediated signal transduction in the regulation of NLRP3 protein expression and caspase-1-mediated interleukin-1β secretion - Pei-Chun Liao; Louis Kuoping Chao; Ju-Ching Chou; Wei-Chih Dong; Chien-Nan Lin; Chai-Yi Lin; Ann Chen; Shuk-Man Ka; Chen-Lung Ho; Kuo-Feng Hua (Inflammation Research, 2013)

Alteration of discoidin domain receptor-2 expression: possible role in peroxynitrite-induced apoptosis in human cerebral vascular smooth muscle cells - Lin Li; Zhiyong Yue; Xiaojuan Wan; Guodong Zhang; Shasha Song; Xiaohui Bai; Yulian Jiao; Yuanrong Ju; Jianfeng Li (Molecular & Cellular Toxicology, 2012)

Invading time of Colletotrichum gloeosporioides affects fruit drop and infection rate in ‘Irwin’ mango (Mangifera indica L.) - Chin-Hsing Chang; Tzong-Shyan Lin; Wen-Ju Yang (Horticulture, Environment, and Biotechnology, 2012)

Coupled dynamics of energy budget and population growth of tilapia in response to pulsed waterborne copper - Wei-Yu Chen; Chia-Jung Lin; Yun-Ru Ju; Jeng-Wei Tsai; Chung-Min Liao (Ecotoxicology, 2012)

Spectra response from macromolecular structure evolution of tectonically deformed coal of different deformation mechanisms - XiaoShi Li; YiWen Ju; QuanLin Hou; Hong Lin (Science China Earth Sciences, 2012)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

Human anti-EGFL7 recombinant full-length antibodies selected from a mammalian cell-based antibody display library - Feng Li; Yan-Hong Liu; Yan-Wen Li; Qian Ju; Lin Chen; Ping-Li Xie; Yue-Hui Li; Guan-Cheng Li (Molecular and Cellular Biochemistry, 2012)

Astragaloside IV prevents MPP+-induced SH-SY5Y cell death via the inhibition of Bax-mediated pathways and ROS production - Zhi-guo Zhang; Lin Wu; Ju-lei Wang; Jian-dong Yang; Jing Zhang; Jian Zhang; Li-hong Li; Yi Xia; Li-bo Yao; Huai-zhou Qin; Guo-dong Gao (Molecular and Cellular Biochemistry, 2012)

Biotransformation of ginsenosides Re and Rg1 into ginsenosides Rg2 and Rh1 by recombinant β-glucosidase - Lin-Hu Quan; Jin-Woo Min; Subramaniyam Sathiyamoorthy; Dong-Uk Yang; Yeon-Ju Kim; Deok-Chun Yang (Biotechnology Letters, 2012)

Effect of C-terminal truncation on enzyme properties of recombinant amylopullulanase from Thermoanaerobacter pseudoethanolicus - Fu-Pang Lin; Yi-Hsuan Ho; Hsu-Yang Lin; Hui-Ju Lin (Extremophiles, 2012)

Oxidative stress in greater duckweed (Spirodela polyrhiza) caused by long-term NaCl exposure - In-Hwa Chang; Kai-Teng Cheng; Po-Chuan Huang; Yen-Yu Lin; Lee-Ju Cheng; Tai-Sheng Cheng (Acta Physiologiae Plantarum, 2012)

Mutation of the Nrf2 gene in non-small cell lung cancer - Yi Hu; Yanfang Ju; Dongmei Lin; Zhikuan Wang; Yurong Huang; Sujie Zhang; Chao Wu; Shunchang Jiao (Molecular Biology Reports, 2012)

PC-based artificial neural network inversion for airborne time-domain electromagnetic data - Kai-Guang Zhu; Ming-Yao Ma; Hong-Wei Che; Er-Wei Yang; Yan-Ju Ji; Sheng-Bao Yu; Jun Lin (Applied Geophysics, 2012)

High incidence of acute promyelocytic leukemia specifically induced by N-nitroso-N-methylurea (NMU) in Sprague–Dawley rats - Yun-Ching Chang; Jeng-Dong Hsu; Wea-Lung Lin; Yi-Ju Lee; Chau-Jong Wang (Archives of Toxicology, 2012)

QTL detection of seven quality traits in wheat using two related recombinant inbred line populations - Jun Li; Fa Cui; An-ming Ding; Chun-hua Zhao; Xiu-qin Wang; Lin Wang; Yin-guang Bao; Xiao-lei Qi; Xing-feng Li; Ju-rong Gao; De-shun Feng; Hong-gang Wang (Euphytica, 2012)

Investigations on the Interaction between Cuprous Oxide Nanocubes and Bovine Serum Albumin with Comprehensive Spectroscopic Methods - Peng Ju; Hai Fan; Tao Liu; Lin Cui; Shiyun Ai; Xiaona Wu (Biological Trace Element Research, 2011)

In vitro shoot induction and plant regeneration from flower buds in Paphiopedilum orchids - Yu-Ju Liao; Yu-Ching Tsai; Yung-Wei Sun; Ruey-Song Lin; Fang-Sheng Wu (In Vitro Cellular & Developmental Biology - Plant, 2011)

Nitric oxide activates superoxide dismutase and ascorbate peroxidase to repress the cell death induced by wounding - Chih-Ching Lin; Pei-Ju Jih; Hsin-Hung Lin; Jeng-Shane Lin; Ling-Lan Chang; Yu-Hsing Shen; Shih-Tong Jeng (Plant Molecular Biology, 2011)

Genetic diversity and positive selection analysis of classical swine fever virus isolates in south China - Haiyan Shen; Jingjing Pei; Jialin Bai; Mingqiu Zhao; Chunmei Ju; Lin Yi; Yanmei Kang; Xuetao Zhang; Lijun Chen; Yinguang Li; Jiaying Wang; Jinding Chen (Virus Genes, 2011)

Genetic evidence for involvement of the alternative sigma factor SigI in controlling expression of the cell wall hydrolase gene lytE and contribution of LytE to heat survival of Bacillus subtilis - Chi-Ling Tseng; Jung-Tze Chen; Ju-Hui Lin; Wan-Zhen Huang; Gwo-Chyuan Shaw (Archives of Microbiology, 2011)

Molecular and morphological evidences reveal a cryptic species in the Vinaceous Rosefinch Carpodacus vinaceus (Fringillidae; Aves) - Hsu‐Chun Wu; Rong‐Chien Lin; Hsin‐Yi Hung; Chia‐Fen Yeh; Jui‐Hua Chu; Xiao‐Jun Yang; Chiou‐Ju Yao; Fa‐Sheng Zou; Cheng‐Te Yao; Shou‐Hsien Li; Fu‐Min Lei (Zoologica Scripta, 2011)
Wu, H.‐C., Lin, R.‐C., Hung, H.‐Y., Yeh, C.‐F., Chu, J.‐H., Yang, X.‐J., Yao, C.‐J., Zou, F.‐S., Yao, C.‐T., Li, S.‐H. & Lei, F.‐M. (2011). Molecular and morphological evidences reveal a cryptic species in the Vinaceous Rosefinch Carpodacus vinaceus (Fringillidae; Aves). — Zoologica Scripta, 40 , 468–478. The Vinaceous Rosefinch ( Carpodacus vinaceus ) is endemic in East Asia with two recognized subspecies – C. v. vinaceus , distributed along the eastern edge of the Tibetan Plateau and the Himalayas, and C. v. formosanus , restricted to Taiwan’s Central Mountain Range. As reflected in a controversial taxonomic history, this vastly disjunctive distribution pattern suggests that the subspecies, having been isolated from each other for a long time, might have diverged, challenging the current taxonomic treatment and calling for possible species delimitation. Sequences of two mitochondrial fragments (mtDNA) and two Z‐linked nuclear loci (zDNA) were used to reconstruct the intraspecific phylogeny of C. vinaceous . The mtDNA tree shows that the two subspecies of the vinaceous rosefinch form two exclusively monophyletic clades. All but one zDNA sequences from the nominate subspecies and C. v. formosanus also formed exclusively monophyletic clades (the exceptional zDNA sequence from C. v. vinaceous formed a weakly supported clade with two outgroup species). Moreover, by conducting quantitative comparisons of morphometric traits and male plumage coloration, we found that the two subspecies exhibit distinguishable morphological differences. All the evidence therefore suggests that C. v. formosanus is a cryptic species and that its taxonomic status should be restored to full species. Molecular dating suggests that the two sibling rosefinches split 1.7 ± 0.2 million years ago, providing a point estimate for the historical connectivity of biota between eastern Tibet‐Himalayas and montane Taiwan.

Estimation of cancer cases and deaths attributable to infection in China - Wang Xiang; Ju-Fang Shi; Ping Li; Jian-Bing Wang; Li-Na Xu; Wen-Qiang Wei; Fang-Hui Zhao; You-Lin Qiao; Paolo Boffetta (Cancer Causes & Control, 2011)

Assessing abalone growth inhibition risk to cadmium and silver by linking toxicokinetics/toxicodynamics and subcellular partitioning - Wei-Yu Chen; Yun-Ru Ju; Bo-Ching Chen; Jeng-Wei Tsai; Chia-Jung Lin; Chung-Min Liao (Ecotoxicology, 2011)

Molecular epidemiology of Echovirus 30 in Taiwan, 1988–2008 - Guan-Ming Ke; Kuei-Hsiang Lin; Po-Liang Lu; Yi-Chin Tung; Chu-Feng Wang; Liang-Yin Ke; Min-Sheng Lee; Pei-Chin Lin; Hui-Ju Su; Yi-Ying Lin; Tzu-Ping Huang; Jen-Ren Wang; et al. (Virus Genes, 2011)

Comparison in eccentric exercise-induced muscle damage among four limb muscles - Trevor C. Chen; Kun-Yi Lin; Hsin-Lian Chen; Ming-Ju Lin; Kazunori Nosaka (European Journal of Applied Physiology, 2011)

Higher rates of nitrogen fertilization decrease soil enzyme activities, microbial functional diversity and nitrification capacity in a Chinese polytunnel greenhouse vegetable land - Weishou Shen; Xiangui Lin; Weiming Shi; Ju Min; Nan Gao; Huayong Zhang; Rui Yin; Xinhua He (Plant and Soil, 2010)

Hijacking the endocytic machinery by microbial pathogens - Ann En-Ju Lin; Julian Andrew Guttman (Protoplasma, 2010)

Alleviation of ovariectomy-induced osteoporosis in rats by Panax notoginseng saponins - Yang Shen; Yong-Qi Li; Shao-Ping Li; Lin Ma; Li-Ju Ding; Hui Ji (Journal of Natural Medicines, 2010)

Proteomic Analysis of Interactions Between the Generalist Herbivore Spodoptera exigua (Lepidoptera: Noctuidae) and Arabidopsis thaliana - Ju-Hong Zhang; Li-Wen Sun; Lin-Lin Liu; Jie Lian; Shao-Li An; Xu Wang; Jing Zhang; Jun-Ling Jin; Shan-Yu Li; Jing-Hui Xi (Plant Molecular Biology Reporter, 2010)

A Simple Allometric Diffusion-Based Biokinetic Model to Predict Cu(II) Uptake Across Gills of Freshwater Clam Corbicula fluminea - W.-Y. Chen; C.-M. Lin; Y.-R. Ju; C.-M. Liao (Bulletin of Environmental Contamination and Toxicology, 2010)

Expression analysis of shikonin-biosynthetic genes in response to M9 medium and light in Lithospermum erythrorhizon cell cultures - Wen-Ju Zhang; Jing Su; Meng-Yue Tan; Gen-Lin Liu; Yan-Jun Pang; Heng-Guan Shen; Jin-Liang Qi; Yonghua Yang (Plant Cell, Tissue and Organ Culture (PCTOC), 2010)

Caligus ignotus n. sp. (Copepoda: Caligidae) parasitic on Poey’s scabbardfish Evoxymetopon poeyi (Günther) off Taiwan - Ju-shey Ho; Ching-Long Lin (Systematic Parasitology, 2010)

Composition, spatial distribution, and environmental significance of water ions in Pumayum Co catchment, southern Tibet - Liping Zhu; Jianting Ju; Yong Wang; Manping Xie; Junbo Wang; Ping Peng; Xiaolin Zhen; Xiao Lin (Journal of Geographical Sciences, 2010)

Magnesium sulfate enhances exercise performance and manipulates dynamic changes in peripheral glucose utilization - Shiu-Min Cheng; Lin-Lan Yang; Sy-Huah Chen; Mei-Hsiang Hsu; I-Ju Chen; Fu-Chou Cheng (European Journal of Applied Physiology, 2010)

Impact of GPS radio occultation data assimilation on regional weather predictions - Ching-Yuang Huang; Ying-Hwa Kuo; Shu-Ya Chen; Chuen-Tsyr Terng; Fang-Ching Chien; Pay-Liam Lin; Mien-Tze Kueh; Shu-Hua Chen; Ming-Jen Yang; Chieh-Ju Wang; Anisetty S. K. A. V. Prasad Rao (GPS Solutions, 2010)

Model analyses of visual biofeedback training for EEG-based brain-computer interface - Chih-Wei Chen; Ming-Shaung Ju; Yun-Nien Sun; Chou-Ching K. Lin (Journal of Computational Neuroscience, 2009)

Isolation and characterization of microsatellites in Chinese white olive (Canarium album) and cross-species amplification in Canarium pimela - Xin Zhang; Wan-Hui Ye; Hong-Lin Cao; Zheng-Feng Wang; Hao Shen; Ju-Yu Lian (Conservation Genetics, 2009)

Human papillomavirus type-distribution in cervical cancer in China: the importance of HPV 16 and 18 - Wen Chen; Xun Zhang; Anco Molijn; David Jenkins; Ju-Fang Shi; Wim Quint; Johannes E. Schmidt; Ping Wang; Yu-Ling Liu; Lian-Kun Li; Hong Shi; Ji-Hong Liu; et al. (Cancer Causes & Control, 2009)

Investigation of bathymetry and water quality of Lake Nam Co, the largest lake on the central Tibetan Plateau, China - Junbo Wang; Liping Zhu; Gerhard Daut; Jianting Ju; Xiao Lin; Yong Wang; Xiaolin Zhen (Limnology, 2009)

A vitronectin M381T polymorphism increases risk of hemangioblastoma in patients with VHL gene defect - Jing-Shan Huang; Chih-Ming Lin; Yu-Che Cheng; Kun-Long Hung; Chih-Cheng Chien; Shao-Kuan Chen; Chih-Ju Chang; Chan-Wei Chen; Chi-Jung Huang (Journal of Molecular Medicine, 2009)

Isolation and characterization of polymorphic microsatellite loci in Candidia barbata (Cyprinidae) using PCR-based isolation of microsatellite arrays (PIMA) - Tzen-Yuh Chiang; Yu-Min Ju; Lee-Shing Fang; Chung-Jian Lin (Conservation Genetics, 2009)

Muscle damage responses of the elbow flexors to four maximal eccentric exercise bouts performed every 4 weeks - Trevor C. Chen; Hsin-Lian Chen; Ming-Ju Lin; Chang-Jun Wu; Kazunori Nosaka (European Journal of Applied Physiology, 2009)

Overexpression of Thellungiella halophila H+-PPase (TsVP) in cotton enhances drought stress resistance of plants - Su-Lian Lv; Li-Jun Lian; Pei-Lin Tao; Zhao-Xia Li; Ke-Wei Zhang; Ju-Ren Zhang (Planta, 2009)

The predictive role of E2-EPF ubiquitin carrier protein in esophageal squamous cell carcinoma - Miao-Fen Chen; Kuan-Der Lee; Ming-Shian Lu; Chih-Cheng Chen; Ming-Ju Hsieh; Yun-Hen Liu; Paul-Yang Lin; Wen-Cheng Chen (Journal of Molecular Medicine, 2009)

Genetic analysis of H3 subtype influenza viruses isolated from domestic ducks in northern China during 2004–2005 - Juan Pu; Qin-Fang Liu; Ying-Ju Xia; Yu-Lei Fan; Earl G. Brown; Fu-Lin Tian; Jin-Hua Liu (Virus Genes, 2009)

A revision of the family Dissonidae Kurtz, 1924 (Copepoda: Siphonostomatoida) - Geoff A. Boxshall; Ching-Long Lin; Ju-Shey Ho; Susumu Ohtsuka; B. A. Venmathi Maran; Jean-Lou Justine (Systematic Parasitology, 2008)

Cloning, Structure, and Expression Pattern of the P-450 Aromatase Gene in Rice Field Eel (Monopterus albus) - Ju-Hua Yu; Yong-Kai Tang; Jian-Lin Li (Biochemical Genetics, 2008)

Desferoxamine preconditioning protects against cerebral ischemia in rats by inducing expressions of hypoxia inducible factor 1α and erythropoietin - Yun-Xia Li; Su-Ju Ding; Lin Xiao; Wei Guo; Qing Zhan (Neuroscience Bulletin, 2008)

Analysis of Acropora muricata Calmodulin (CaM) Indicates That Scleractinian Corals Possess the Ancestral Exon/Intron Organization of the Eumetazoan CaM Gene - Chih-Yung Chiou; I-Ping Chen; Chienhsun Chen; Henry Ju-Lin Wu; Nuwei Vivian Wei; Carden C. Wallace; Chaolun Allen Chen (Journal of Molecular Evolution, 2008)

Complete sequence of a subgroup 3.4 strain of classical swine fever virus from Taiwan - Yu-Ju Lin; Maw-Sheng Chien; Ming-Chung Deng; Chin-Cheng Huang (Virus Genes, 2007)

Highly efficient Agrobacterium-mediated transformation of embryogenic cell suspensions of Musa acuminata cv. Mas (AA) via a liquid co-cultivation system - Xia Huang; Xue-Lin Huang; Wang Xiao; Jie-Tang Zhao; Xue-Mei Dai; Yun-Feng Chen; Xiao-Ju Li (Plant Cell Reports, 2007)

Adaptation of agriculture to warming in Northeast China - Xiu Yang; Erda Lin; Shiming Ma; Hui Ju; Liping Guo; Wei Xiong; Yue Li; Yinlong Xu (Climatic Change, 2007)

Three species of Caligus Müller, 1785 (Copepoda: Caligidae) parasitic on Caranx spp. (Teleostei: Carangidae) off Taiwan - Ju-shey Ho; Chin-Long Lin (Systematic Parasitology, 2007)

Osteogenic differentiation of adipose derived stem cells promoted by overexpression of osterix - Ling Wu; Yao Wu; Yunfeng Lin; Wei Jing; Xin Nie; Ju Qiao; Lei Liu; Wei Tang; Weidong Tian (Molecular and Cellular Biochemistry, 2007)

Interleukin-18 gene polymorphism, but not interleukin-2 gene polymorphism, is associated with rheumatoid arthritis - Cheng-Chun Lee; Wei-Yong Lin; Lei Wan; Yuhsin Tsai; Ying-Ju Lin; Chang-Hai Tsai; Chung-Ming Huang; Fuu-Jen Tsai (Immunogenetics, 2007)

Two new species of taeniacanthid copepods (Poecilostomatoida) parasitic on marine fishes of Taiwan - Ju-shey Ho; Ching-Long Lin (Systematic Parasitology, 2007)

Model-based ankle joint angle tracing by cuff electrode recordings of peroneal and tibial nerves - Chou-Ching K. Lin; Ming-Shaung Ju; Hang-Shing Cheng (Medical & Biological Engineering & Computing, 2007)

Climate change and critical thresholds in China’s food security - Wei Xiong; Erda Lin; Hui Ju; Yinlong Xu (Climatic Change, 2007)

Induction and cryopreservation of embryogenic cultures from nucelli and immature cotyledon cuts of mango (Mangifera indica L. var Zihua) - Yong-Jie Wu; Xue-Lin Huang; Qi-Zhu Chen; Xiao-Ju Li; Florent Engelmann (Plant Cell Reports, 2007)

Pluripotency potential of human adipose-derived stem cells marked with exogenous green fluorescent protein - Yunfeng Lin; Lei Liu; Zhiyong Li; Ju Qiao; Ling Wu; Wei Tang; Xiaohui Zheng; Xizhe Chen; Zhengbin Yan; Weidong Tian (Molecular and Cellular Biochemistry, 2006)

Tie them up tight: wrapping by Philoponella vicina spiders breaks, compresses and sometimes kills their prey - William G. Eberhard; Gilbert Barrantes; Ju-Lin Weng (The Science of Nature, 2006)

Multilineage differentiation of adipose-derived stromal cells from GFP transgenic mice - Yunfeng Lin; Xizhe Chen; Zhengbin Yan; Lei Liu; Wei Tang; Xiaohui Zheng; Zhiyong Li; Ju Qiao; Shengwei Li; Weidong Tian (Molecular and Cellular Biochemistry, 2006)

Expression of exogenous or endogenous green fluorescent protein in adipose tissue-derived stromal cells during chondrogenic differentiation - Yunfeng Lin; Weidong Tian; Xizhe Chen; Zhengbin Yan; Zhiyong Li; Ju Qiao; Lei Liu; Wei Tang; Xiaohui Zheng (Molecular and Cellular Biochemistry, 2005)

Inhibitory effect of trilinolein on endothelin-1-induced c-fos gene expression in cultured neonatal rat cardiomyocytes - Hung-Yu Yang; Ju-Chi Liu; Yen-Ling Chen; Cheng-Hsien Chen; Heng Lin; Jia-Wei Lin; Wen-Ta Chiu; Jin-Jer Chen; Tzu-Hurng Cheng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2005)

Investigation of Mtbe and Aromatic Compound Concentrations at a Gas Service Station - Chi-Wen Lin; Song-Bor Chiang; San-Ju Lu (Environmental Monitoring and Assessment, 2005)

Polymorphic Study of Equine Antiviral MXA Gene - Lin Hua Ju; Akio Onogi; Junji Ueda; Koji Yamada; Yuichiro Nakatsu; Mika Ohe; Hiroshi Hata; Kazuya Sasaki; Tomomasa Watanabe (Biochemical Genetics, 2005)

A Continuous Mapping of Tidal Current Structures in the Kanmon Strait - Keisuke Yamaguchi; Ju Lin; Arata Kaneko; Tokuo Yayamoto; Noriaki Gohda; Hong-Quang Nguyen; Hong Zheng (Journal of Oceanography, 2005)

Anti-hepatitis B surface antigen IgG1 subclass is predominant in individuals who have recovered from hepatitis B virus infection, chronic carriers and vaccinees - Lina Wang; Shyh-Jye Lin; Ju-Hsin Tsai; Chung-Hung Tsai; Chung-Chuan Tsai; Chi-Chiang Yang (Medical Microbiology and Immunology, 2005)

Molecular diversity of methanotrophs in Transbaikal soda lake sediments and identification of potentially active populations by stable isotope probing - Ju‐Ling Lin; Stefan Radajewski; Bulat T. Eshinimaev; Yuri A. Trotsenko; Ian R. McDonald; J Colin Murrell (Environmental Microbiology, 2004)
Summary Soda lakes are an environment with an unusually high pH and often high salinity. To identify the active methanotrophs in the Soda lake sediments, sediment slurries were incubated with a 10% (v/v) 13 CH 4 headspace and the 13 C‐labelled DNA was subsequently extracted from these sediments following CsCl density gradient centrifugation. This DNA was then used as a template for PCR amplification of 16S rRNA genes and genes encoding PmoA and MmoX of methane monooxygenase, key enzymes in the methane oxidation pathway. Phylogenetic analysis of 16S rRNA genes, PmoA and MmoX identified that strains of Methylomicrobium , Methylobacter , Methylomonas and ‘Methylothermus’ had assimilated the 13 CH 4 . Phylogenetic analysis of PmoA sequences amplified from DNA extracted from Soda lake sediments before Stable Isotope Probing (SIP) treatment showed that a much wider diversity of both type I and type II methanotroph sequences are present in this alkaline environment. The majority of methanotroph sequences detected in the 13 C‐DNA studies were from type I methanotrophs, with 50% of 16S rRNA clones and 100% of pmoA clones from both Lake Suduntuiskii Torom and Lake Gorbunka suggesting that the type I methanotrophs are probably responsible for the majority of methane oxidation in this environment.

Direct somatic embryogenesis induced from cotyledons of mango immature zygotic embryos - Jie-Ning Xiao; Xue-Lin Huang; Yong-Jie Wu; Xiao-Ju Li; Ming-De Zhou; Florent Engelmann (In Vitro Cellular & Developmental Biology - Plant, 2004)

Inhibitory effect of resveratrol on angiotensin II-induced cardiomyocyte hypertrophy - Tzu-Hurng Cheng; Ju-Chi Liu; Heng Lin; Neng-Lang Shih; Yen-Ling Chen; Meng-Ting Huang; Paul Chan; Ching-Feng Cheng; Jin-Jer Chen (Naunyn-Schmiedeberg's Archives of Pharmacology, 2004)

Naricolax insolitus n. sp., a bomolochid copepod (Poecilostomatoida) parasitic in the nasal cavities of silver pomfret Pampus argenteus off Taiwan - Ju-shey Ho; Ching-Long Lin (Systematic Parasitology, 2003)

Characterization of stress-responsive genes, hrcA-grpE-dnaK-dnaJ , from phytopathogenic Xanthomonas campestris - Shu-Fen Weng; Pan-Ming Tai; Cheng-Hwa Yang; Cheng-Der Wu; Wan-Ju Tsai; Juey-Wen Lin; Yi-Hsiung Tseng (Archives of Microbiology, 2001)

Propagation of yellow grouper nervous necrosis virus (YGNNV) in a new nodavirus‐susceptible cell line from yellow grouper, Epinephelus awoara (Temminck & Schlegel), brain tissue - Y‐S Lai; S Murali; H‐C Chiu; H‐Y Ju; Y‐S Lin; S‐C Chen; I‐C Guo; K Fang; C‐Y Chang (Journal of Fish Diseases, 2001)
A nodavirus was isolated from diseased yellow grouper, Epinephelus awoara , larvae cultured in southern Taiwan. The histopathology and RT–PCR results confirmed that it was a fish nodavirus; its coat protein gene sequence was similar to that of red spotted grouper nervous necrosis virus (RGNNV) and it is named yellow grouper nervous necrosis virus (YGNNV). A new nodavirus‐susceptible cell line, grouper brain (GB) was established and characterized from the brain tissue of yellow grouper. The GB cells multiplied well in Leibovitz’s L‐15 medium supplemented with 10% foetal bovine serum at temperatures between 24 and 32 °C, and have been subcultured more than 80 times, becoming a continuous cell line. The GB cell line consists of fibroblast‐like cells and some epithelioid cells. The cell line yielded titres of YGNNV up to 10 8.5 TCID 50 mL –1 . The GB cells effectively replicated the virus at 28 °C, which could be purified to homogeneity by caesium chloride gradient centrifugation. Electron microscopy studies showed that purified virus particles were 25–30 nm in diameter. The cytoplasm of infected cells was filled with aggregates of virus particles. These results indicate that the GB cell line is a significant tool for the study of fish nodaviruses.

The Heterogeneity in Risk Factors of Lung Cancer and the Difference of Histologic Distribution between Genders in Taiwan - Chien-Hung Lee; Ying-Chin Ko; Li Shu-Chuan Cheng; Ying-Chao Lin; Hsiang-Ju Lin; Ming-Shyan Huang; Jhi-Juh Huang; Eing-Long Kao; Hwei-Zu Wang (Cancer Causes & Control, 2001)

Species of Caligus Müller, 1785 (Copepoda: Caligidae) parasitic on marine fishes of Taiwan - Ju-shey Ho; Ching-Long Lin; Shiu-Nan Chen (Systematic Parasitology, 2000)

Polymorphic microsatellite loci and low-invasive DNA sampling inMacaca cyclopis - Jui-Hua Chu; Hai-Yin Wu; Yi-Ju Yang; Osamu Takenaka; Yao-Sung Lin (Primates, 1999)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)